Polyorganosiloxane copolymers with organic polymers
Patent Information
- Application Number
- JP2024550289
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-02-25
- Publication Date
- 2025-03-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
である。これに関して、本発明は、金属クラッド積層体の製造において、利用可能な従来技術の全く範囲内である。新規であるものは、当該の金属クラッド積層体の製造のための式(I)の共重合体の使用であり、これは、現在まで知られていない。
Smart Images

Figure 2025506825000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to hydrolytically stable, curable copolymers of three-dimensionally crosslinked polyorganosiloxanes with polyarylene ethers, their preparation and use for the manufacture of components for high frequency applications.
[0002] The advanced development of high frequency technology for wireless communication increases the need for suitable materials for its implementation. This concerns the whole field of materials such as copper foil, binders, glass fibers, etc. In the case of binders, epoxy resins, which were previously used for the production of both soft and hard metal foil clads, especially copper foil clad laminates, or as a result for the production of printed circuit boards, can no longer be used due to their excessively high dielectric loss factor. Polytetrafluoroethylene, which has a very low dielectric loss factor and is therefore of great utility from the point of view of high frequency applications, has other drawbacks, in particular poor processability and poor bonding properties, which makes it desirable to find an alternative. Polyarylene ethers, which combine low dielectric loss factors with excellent mechanical and thermal properties as well as water repellency, are currently being intensively exploited as binders for this field of application.
[0003] In addition, other organic polymers are being considered in the current development work for this application, such as bismaleimide polymers, bismaleimide-triazine copolymers and hydrocarbon resins, among others, which could also be added to this list.
[0004] Polyorganosiloxanes essentially have excellent heat resistance, weather stability and hydrophobicity, are flame retardant and have low dielectric loss factors.
[0005] These property profiles qualify both the mentioned organic polymers and polyorganosiloxanes for use as binders for the production of high frequency copper foil clad laminates and components such as printed circuit boards and antennas. It is therefore obvious to combine the beneficial properties of these material classes, in this case polyarylene ethers, in order to symbiotically increase in particular their performance. Corresponding attempts have already been described in the prior art.
[0006] The key problem here is to combine polysiloxanes and polyarylene ethers with each other in such a way that they are compatible with each other and do not separate.Physical mixtures often do not meet this prerequisite.In particular, only polysiloxanes with a high degree of aromatic substitution are suitable for such a mixing method.Since aliphatic substituents often result in better dielectric properties, and small aliphatic silicon-bonded radicals, such as methyl radicals in particular, are responsible for particularly low material shrinkage in the event of fire or leave a particularly high mass fraction as combustion residue from the corresponding polysiloxanes, a method that allows the combination of any desired polysiloxane with polyarylene ether has obvious advantages.Such a method consists in the copolymerization of polysiloxanes with polyarylene ethers.In this regard, there is already prior art. [Background technology]
[0007] US Patent No. 5,357,022 teaches flame-retardant thermoplastic polyorganosiloxane-polyarylene ether block copolymers produced from polydiorganosiloxane macromonomers each having two terminal 2-methoxy-4-trimethylenephenol groups and 2,6-xylenol groups obtained by oxidative coupling. Polydiorganosiloxanes of different chain lengths are found to be useful for obtaining the inventive effect of flame retardancy. The hydroxyaryl-terminated polydiorganosiloxanes used by the invention for copolymer synthesis are obtained by hydrosilylation of allyl-functional phenols, such as eugenol, with Si-H-terminated polydiorganosiloxanes.
[0008] No. 8,017,697 teaches that the yield of polyarylene ether-polydiorganosiloxane block copolymers by the method according to U.S. Pat. No. 5,357,022 is very low, because an overwhelming physical mixture of the polyarylene ether and silicone components used is produced, which in some cases has only limited miscibility, and that the inventive effect of flame retardancy according to U.S. Pat. No. 5,357,022 has great potential for improvement, the realization of which is the teaching of U.S. Pat. No. 8,017,697.
[0009] Neither the copolymers according to U.S. Patent No. 5,357,022 nor those according to U.S. Patent No. 8,017,697 have free radical crosslinkable olefinically unsaturated groups for chemical curing. All that remains for further chemical reaction are the phenolic groups of the terminal 2,6-xylenol units.
[0010] The known conventional methods for crosslinking and curing such polyarylene ethers are those using the addition of an excess amount of a thermosetting resin such as an epoxy resin or a crosslinking compound such as triallylisocyanurate, although the properties of low dielectric loss factor, low relative dielectric constant and high heat resistance inherent to polyarylene ethers cannot be achieved by these methods. For example, polyarylene ether / polyepoxide compositions are disclosed in JP-A-6-206984 and JP-A-11-302529. These methods bring about crosslinking and curing by adding an excess amount of polyepoxide to polyarylene ether, and therefore cannot achieve the properties of low dielectric loss factor, low relative dielectric constant and high heat resistance inherent to polyarylene ethers. JP-A-11-236430 discloses a composition consisting of polyarylene ether, a brominated epoxy compound and an allyl compound, but the problem here is that the inherent properties of low dielectric loss factor, low dielectric constant and high heat resistance of polyarylene ether are deteriorated due to the high proportion of epoxy compound and allyl compound in the composition.
[0011] Therefore, the polydiorganosiloxane-polyarylene ether copolymer according to US Patent No. 5,357,022 is not suitable for use in high frequency applications due to these curing characteristics.In addition, polydiorganosiloxane itself is a soft structural element that exerts a softening effect on the copolymer and reduces its glass transition temperature.This causes a reduction in glass transition temperature, which means processing disadvantages for binders for electronic components, such as copper foil clad laminates for manufacturing printed circuit boards.This is because binders with low softening temperatures tend to flow under soldering conditions and will leave holes in electronic components.This makes the printed circuit board unusable.
[0012] US 2018 / 0155547 teaches thermoplastic blends consisting of polyarylene ethers, polyarylene ether-polysiloxane block copolymers, homopolystyrene, flame retardant and reinforcing fillers. The inventive blends according to US 2018 / 0155547 have a balance between the properties of flame retardancy, heat resistance, toughness and melt flow. US 2018 / 0155547, like US 8,017,697, is a thermoplastic blend of C1-C 12 Hydrocarbyl radicals and C1-C 12 The polyarylene ether-polysiloxane block copolymers are interpreted similarly to those from U.S. Pat. Nos. 5,357,022 and 8,017,697, although halohydrocarbyl radicals as well as silicon-bonded hydrogen on the polysiloxane chains of the structure are permitted.
[0013] [ka]
[0014] As in US Pat. No. 5,357,022, the blocks are also linear polysiloxane blocks here, and thus essentially water-substituted polydiorganosiloxanes, if necessary. The polyorganosiloxane units used in the synthesis are again hydroxyaryl-terminated, so that oxidative coupling with further phenol units is possible. In contrast to US Pat. No. 5,357,022, US Pat. App. Pub. No. 2018 / 0155547 allows hydroxyaryl-terminated radicals not only at the end of the polysiloxane chain, but also in the polysiloxane chain. Thus, according to US Pat. App. Pub. No. 2018 / 0155547, not only linear block copolymers are possible, as in US Pat. No. 5,357,022, but also branched block copolymer structures resulting from the growth of polyarylene chains, not only on terminal hydroxyaryl radicals, but also on hydroxyaryl radicals linked on the chain as a result of oxidative coupling.
[0015] Moreover, the polyorganosiloxane according to US 2018 / 0155547 does not contain any organic functional groups that allow further chemical curing, in particular olefinic groups that allow free radical curing. Due to the considerable similarity of the polyorganosiloxane structures according to US 2018 / 0155547 and US 5,357,022, it can be clearly deduced that the hydroxyaryl-functional polyorganosiloxane for the preparation of polyarylene ether-polysiloxane block copolymers according to US 2018 / 0155547 is similarly prepared by hydrosilylation from an allyl-functional phenol and a Si-H-functional polydiorganosiloxane, in particular because the same inventors explicitly mention it in US 8,017,697 and the structure specified therein, which coincides with that of US 2018 / 0155547. In addition, US Patent Publication No. 2018 / 0155547 also allows for Si-H groups in the polyorganosiloxane chain and chain-linked hydroxyaryl radicals, which is clear. If chain-linked Si-H groups are present in the polydiorganosiloxane, they will be partially involved in this hydrosilylation reaction, thus resulting in chain-linked hydroxyaryl radicals, which are responsible for the branching made possible by the invention due to the polyphenylene ether chains grown laterally in the polyarylene ether polysiloxane block copolymer. General formula RSiO 3 / 2 T units or forms of SiO 4 / 2 The branching in the polyorganosiloxane units, called Q units, does not exist in the block copolymers, but in the generalized form RSiO 2 / 2 Rather, there is a single siloxane unit, commonly referred to as a D unit, of the above siloxane units described above.
[0016] The polyarylene ether-polysiloxane block copolymers according to US 2018 / 0155547 A, like the polyarylene ether-polysiloxane block copolymers according to US 5,357,022 and US 8,017,697, do not have further functional groups that allow chemical curing, in particular free radical curing, except for phenolic OH end groups, which are further associated with the same disadvantages with regard to the dielectric properties already mentioned above.
[0017] U.S. Pat. No. 8,309,655 describes the synthesis of polyarylene ether-polysiloxane block copolymers that are not obtained by the oxidative coupling of hydroxyaryl-functional polysiloxanes with phenols, but by the reaction of α,ω-hydroxy-terminated polyarylene ethers with α,ω-hydroxyaryl-terminated polyorganosiloxanes and aromatic dicarbonyl chlorides.
[0018] [ka]
[0019] The hydroxyaryl-terminated polyorganosiloxane used has the structure shown above, R 7 is C1~C 12 Hydrocarbyl radicals and C1-C 12 It may be a halohydrocarbyl radical as well as silicon-bonded hydrogen, in which case the formation reaction designated for the hydroxyaryl-terminated polysiloxane is a hydrosilylation reaction.
[0020] The problem in the reaction of α,ω-hydroxy-terminated polyarylene ethers with α,ω-hydroxyaryl-terminated polyorganosiloxanes and aromatic dicarbonyl chlorides is the control of the reaction. As a result of the different reactivities of α,ω-hydroxy-terminated polyarylene ethers and α,ω-hydroxyaryl-terminated polyorganosiloxanes compared to aromatic dicarbonyl chlorides, the composition of the copolymer can only be controlled with a certain lack of sharpness and increased complexity compared to the oxidative coupling method.
[0021] Again, the block copolymers contain only residual phenolic OH groups as functional groups and no further organic functionality, in particular no free-radically curable olefinically unsaturated groups, which is, as a consequence, already a drawback for the electronic high-frequency applications mentioned above.
[0022] In fact, there are several examples of such substitution of oxidative coupling reaction as the production reaction for polyarylene ether-polysiloxane copolymers. For example, JP 61-252214 A describes the preparation of polyarylene ether-polysiloxane copolymers by the reaction of lithiated polyarylene ethers with one-sided chloride-functional siloxane macromonomers. US Patent No. 4,814,392 describes the preparation of polyarylene ether-polysiloxane copolymers by the reaction of anhydride-functional polyarylene ethers with amino-terminated polysiloxanes. US Patent Application Publication No. 2007 / 0208144 describes the synthesis of polyarylene ether-polysiloxane copolymers by the reaction of polyarylene ethers with hydroxyaryl-terminated polysiloxanes in the presence of activated aromatic carbonates. All these synthesis methods have their own inherent disadvantages. Some of these require many reaction steps and the use of expensive and limited availability chemicals, the handling of which would cause considerable problems on an industrial scale and would incur additional complexity and costs.Therefore, the replacement of oxidative coupling as the process of choice for the preparation of polyarylene ethers and their derivatives or variants has not been established.Apart from this, exclusively linear polysiloxane structures are used in these documents and teachings, namely polydiorganosiloxanes with terminal functional groups.Neither crosslinked siloxane structures are obtained, nor are there any mentions of further functional groups, especially olefinically unsaturated functional groups suitable for free radical curing. Summary of the Invention
[0023] Objective of the present invention: It is an object of the present invention to provide hydrolytically stable copolymers of three-dimensionally crosslinked polyorganosiloxanes and polyarylene ethers that are chemically curable to thermosetting resins, and methods for their preparation and use for the manufacture of components for high frequency applications.
[0024] The present invention relates to a compound of formula (I): [O 3-a / 2 R a Si-Y1 (SiR a O 3-a / 2 ) b ] c (R 1 SiO 3 / 2 ) d (R 2 2SiO 2 / 2 ) e (R 3 3SiO 1 / 2 ) f (SiO 4 / 2 ) g (I) The polyarylene ether-polysiloxane copolymer containing an olefinically unsaturated group is represented by the formula (I): Y 1 is a divalent to dodecavalent organic unsubstituted or heteroatom-substituted aliphatic, alicyclic or aromatic organic radical having 1 to 24 carbon atoms and bonded to a silicon atom by a chemical bond or a Si bond, R, R 1 , R 2 and R 3 are independently the same or different and are a hydrogen radical, a hydroxyl radical, or a monovalent unsubstituted or heteroatom substituted Si—C or Si—O bond, an organic hydrocarbyl radical having 1 to 18 carbon atoms, which may be organofunctional, or a Si—C bonded polyarylene ether radical; Total R, R as 100% by weight 1 , R 2 and R 3 the ratio of the hydroxyl radicals and the Si—O bond radicals to the total amount of radicals is 5% by weight or less; Total R, R as 100% by weight 1 , R 2 and R 3 the proportion of the Si-C bonded polyarylene ether radicals relative to the total number of radicals is at least 10 wt. %; All R, R as 100mol% 1 , R 2 and R 3 the proportion of said olefinically or acetylenically unsaturated radicals relative to the total number of radicals is at least 0.5 mol %; The polyarylene ether radical has formula (II) or (III): [ka] and in the formulae (II) and (III), R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13 The radicals are independently a hydrogen radical, a monovalent hydrocarbyl group, a heteroatom-substituted hydrocarbyl group, an organofunctional radical, or (R 40 3Si-) type silyl group, R 40 is R 3 With the definition of R 4 ~R 12 The radical may be attached to the aromatic ring by a heteroatom; R 4 , R 5 and R 6 The radical may be a chemical bond or a divalent aliphatic, cycloaliphatic or aromatic hydrocarbyl radical having 1 to 12 carbon atoms, whereby the bond of the radical of formula (II) with the polyorganosiloxane backbone is established and at least one R 4 , R 5 or R 6 The radical is a radical that establishes a bond with the polyorganosiloxane backbone, As far as chemically possible, R 4 ~R 12 Adjacent radicals from the radical group may be linked together to form the same cyclic saturated or unsaturated radical to form fused polycyclic structures, including both alicyclic and cyclic aromatic structures or mixed forms thereof; R 14 A radical is a chemical bond or (-C6R 15 4-), where R 15 Independently of these, R9 , R 10 , R 11 Or R 12 has the same meaning as the radical -CR 16 2-form alkylene radical, R 16 is R 15 Independently of R 15 may have the same meaning as -[(OCH2)2O] l -or-[(OCH2CH(CH3)2)O] m divalent glycol radicals of the form -, where l and m are each independently an integer having a value of 1 to 50, inclusive; -Si(R 17 )2O 2 / 2 -divalent silyloxy radicals of the form -[(CH2)3Si-[O-Si(R 18 )2] n Divalent siloxane radicals of the form O-Si(CH2)3-, -Si(R 19 )2-type divalent silyl radicals (wherein R 17 , R 18 and R 19 are mutually independent, R 15 Independently of R 15 and n, in each occurrence, is an integer having a value from 0 to 500 (inclusive); a is an integer having a value of 0, 1 or 2, and the indices a on either side of the Y group may assume these meanings independently of one another, such that different a's may independently have different values within the range of values specified; h has a value from 0 to 1000; b is an integer having a value from 1 to 11; c has a value of 0 to 0.9; d has a value from 0 to 1; e has a value of 0 to 0.5; f has a value of 0 to 0.6; g has a value of 0 to 0.2; c+d+e+f+g=1, where at least c or d has a value other than 0, and the sum of c+d is at least 40% of the sum of c+d+e+f+g; i, in each case, is an integer having a value from 0 to 50, inclusive; j, in each case, is an integer having a value from 0 to 10, inclusive; k, in each case, is an integer having a value from 0 to 50, inclusive; provided that at least one polyarylene ether radical of formula (II) or (III) is present in each polyarylene ether-polysiloxane copolymer of formula (I); A copolymer is provided.
[0025] The polyarylene ether-polysiloxane copolymers of formula (I) are copolymers that are chemically cured into thermosetting resins by three-dimensional crosslinking of olefinic unsaturated groups, polyarylene ethers and polyorganosiloxanes. They overcome and improve the shortcomings recognized in the prior art, since it is possible to omit the addition of auxiliary polymers or other substances for curing that adversely affect dielectric properties, i.e., increase dielectric loss factor and relative dielectric constant, and the curing of the polyarylene ether-polyorganosiloxane copolymers of the present invention as the sole binder provides ready-to-use materials suitable for use in high frequency applications.
[0026] When there is more than one polyarylene ether radical per polyarylene ether-polysiloxane copolymer of formula (I), they can be either solely of formula (II) or solely of formula (III) or a mixture of formulas (II) and (III).
[0027] The arrangement of the structural groups may be random or block. This is because the structural groups [O 3-a / 2 R a Si-Y 1 (SiR a O 3-a / 2 ) b ] c (R 1 SiO 3 / 2 ) d (R 2 2SiO2 / 2 ) e (R 3 3SiO 1 / 2 ) f (SiO 4 / 2 ) g occur randomly with respect to one another in the molecular structure or in both cases have the same form, i.e., [O 3-a / 2 R a Si-Y 1 (SiR a O 3-a / 2 ) b ] c (R 1 SiO 3 / 2 ) d (R 2 2SiO 2 / 2 ) e (R 3 3SiO 1 / 2 ) f (SiO 4 / 2 ) g This means that there are blocks of multiple repeat units of each of the other structural groups, as well as blocks of multiple repeat units of each of the other structural groups which in each case must be combined to form a block in order to obtain the effective block structure, in which case at least three of the same structural groups must be combined to form a block.
[0028] Preferably, independently in each case, the value of d is at least 4, c+f is at least 9, preferably at least 15, in particular 20 to 100, and g is at least 1.
[0029] Preferably, the total R, R is 100% by weight. 1 , R 2 and R 3 The ratio of hydroxyl radicals and Si—O bond radicals to the total number of radicals is 4% by weight or less, more preferably 3% by weight or less, and particularly preferably 2% by weight or less.
[0030] Preferably, the total R, R is 100% by weight. 1 , R 2 and R 3The proportion of Si-C bonded polyarylene ether radicals relative to the total of radicals is at least 12% by weight, more preferably at least 14% by weight, in particular at least 15% by weight. It has been found to be particularly useful to adjust the proportion of polyarylene ether radicals to at least 30% by weight, since this achieves particularly excellent bonding properties of the inventive polyorganosiloxane-polyarylene ether copolymer of formula (I) in its inventive use as a binder for high frequency metal laminates.
[0031] Preferably, all R, R 1 , R 2 and R 3 Of the radicals, at least 2 mol %, more preferably at least 3 mol %, in particular at least 4 mol % are olefinically or acetylenically unsaturated radicals.
[0032] R 4 , R 5 and R 6 A preferred divalent hydrocarbyl radical selected from is the -(CH2)3- radical.
[0033] The polyarylene ether radical of formula (III) may be attached to either only one end or both ends of the polyorganosiloxane backbone of the polyorganosiloxane-polyarylene ether copolymer of formula (I).
[0034] Preferred R 14 Radicals include chemical bonds, -CH2- radicals, -C(CH3)2- radicals, -C(C6H5)2- radicals and -[(CH2)3Si-[O-Si(R 18 )2]O-Si(CH2)3- radical.
[0035] The value of h is preferably 1 to 500, more preferably 1 to 300, and particularly preferably 1 to 150.
[0036] The preferred value of b is 1.
[0037] The preferred value of e is 0 to 0.2.
[0038] The preferred value of f is 0 to 0.5.
[0039] The preferred value of g is <0.2.
[0040] Preferably, the sum of c+d in the sum of c+d+e+f+g accounts for at least 50%.
[0041] Preferably, i has a value of 1-40, more preferably 1-30, and particularly preferably 1-25.
[0042] Preferably, j has a value from 0 to 5.
[0043] Preferably, k has a value of 1-40, more preferably 1-30, and particularly preferably 1-25.
[0044] As pure substances, the inventive polyorganosiloxane-polyarylene ether copolymers of formula (I) preferably have an average molecular weight Mw in the range of 500 to 750000 g / mol, preferably 600 to 600000 g / mol, more preferably 800 to 500000 g / mol and in particular 800 to 40000 g / mol; The polyorganosiloxane-polyarylene ether copolymer of the present invention of formula (I) is solid at 25° C. and has a viscosity at 25° C. of 20 to 8,000,000 mPa, preferably 20 to 5,000,000 mPa, and particularly 20 to 3,000,000 mPa, and the solid polyorganosiloxane containing phenyl groups has a glass transition temperature in the non-crosslinked state in the range of 25° C. to 350° C., preferably 30° C. to 300° C., and particularly 30° C. to 280° C. Particularly suitable polyorganosiloxane-polyarylene ether copolymers of formula (I) have been found to be solid at 25° C. and have a glass transition temperature of 30° C. to 280° C.
[0045] The polyorganosiloxane-polyarylene ether copolymer of the present invention of formula (I) can be dissolved in aromatic solvent at a ratio of at least 30% by weight of the solution.In other words, at least 30 parts of the polyorganosiloxane-polyarylene ether copolymer of the present invention of formula (I) can be dissolved in a solution consisting of 100 parts of the total consisting of the solvent and the polyorganosiloxane-polyarylene ether copolymer of the present invention of formula (I).Examples of suitable solvents are toluene, xylene, ethylbenzene or mixtures thereof.Solubility in other solvents varies depending on the solvent selected and each polyorganosiloxane-polyarylene ether copolymer of the present invention of formula (I), and can vary from insoluble to excellent solubility.
[0046] Preferred alkyl, cycloalkyl and aryl and alkaryl radicals R, R 1 , R 2 , R 3 Selected examples of are methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl radicals, hexyl radicals such as n-hexyl radical, heptyl radicals such as n-heptyl radical, octyl radicals such as n-octyl radical, and isooctyl radicals such as 2,2,4-trimethylpentyl radical, nonyl radicals such as n-nonyl radical, decyl radicals such as n-decyl radical, dodecyl radicals such as n-dodecyl radical, and octadecyl radicals such as n-octadecyl radical, cyclopentyl, cyclohexyl, cycloheptyl and methylcyclohexyl radicals, phenyl, naphthyl, anthryl and phenanthryl radicals, tolyl radical, xylyl radical and ethylphenyl radical, and aralkyl radicals such as benzyl radical, α- and β-phenylethyl radicals.
[0047] Unsubstituted radicals R, R 1 , R 2 , R 3are primarily hydrocarbyl radicals having 1 to 12 carbon atoms, more preferably the methyl, ethyl and n-propyl radicals as well as the phenyl radical, in particular the methyl, n-propyl and phenyl radicals. Particularly preferred are the methyl and phenyl radicals.
[0048] R, R 1 , R 2 and R 3 Preferred heteroatoms which may be present in the radicals are oxygen atoms, more preferred are nitrogen atoms, phosphorus atoms, sulfur atoms and halogen atoms such as chlorine and fluorine atoms.
[0049] Preferred heteroatom-substituted radicals R, R 1 , R 2 , R 3 Examples are glycol radicals, such as polypropylene glycol radicals and polyethylene glycol radicals.
[0050] Preferred organic functional radicals R, R 1 , R 2 , R 3 Selected examples are acrylate and methacrylate radicals such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, t-butyl acrylate, t-butyl methacrylate, 2-ethylhexyl acrylate and norbornyl acrylate, with particular preference being given to methyl acrylate, methyl methacrylate, n-butyl acrylate, isobutyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate and norbornyl acrylate.
[0051] R 2 Further examples of radicals are the olefinically or acetylenically unsaturated hydrocarbyl radicals of formulae (IV) and (V): Z-CR 19=CR 20 R 21 (IV) ZC≡CR 22 (V) In the above formula, Z is a chemical bond or a divalent linear or branched hydrocarbyl radical having up to 30 carbon atoms, Z may contain an olefinically unsaturated group or a heteroatom, and the atom directly bonded to the silicon of the Z radical is carbon. Heteroatom-containing fragments that may typically be present in the Z radical are -COC-, -C(=O)-, -OC(=O)-, -OC(=O)-O-, and asymmetric radicals may be incorporated in the Z radical in any possible orientation, and R 19 , R 20 , R 21 and R 22 is a C1-C8 hydrocarbyl radical which may optionally contain a hydrogen atom or a heteroatom, preferably a hydrocarbyl radical which does not contain a heteroatom, and a hydrogen atom is R 19 , R 20 , R 21 and R 22 is the most preferred radical for. Particularly preferred radicals (IV) are the vinyl, allyl, propenyl and butenyl radicals, especially the vinyl radical. Radical (IV) may also be a dienyl radical linked via a spacer, such as 1,3-butadienyl, or an isoprenyl radical linked via a spacer.
[0052] R, R 1 , R 2 , R 3 A further example of a radical is the silicon-bonded hydrogen of a hydridic.
[0053] Apart from the hydrogen atoms which are always silicon-bonded, R, R 1 , R 2 , R 3 The radicals are generally not directly bonded to the silicon atom. Exceptions to this are made by olefinic or acetylenic groups which may be present in a directly silicon-bonded form, in particular vinyl groups. Other functional groups R, R1 , R 2 , R 3 is bonded to the silicon atom via a spacer group, which is always a Si-C bond, where the spacer is a divalent hydrocarbyl radical comprising 1 to 30 carbon atoms, non-adjacent carbon atoms may be replaced by oxygen atoms, which are not preferred, or may contain other heteroatoms or heteroatom groups.
[0054] Preferably, the methacrylate and acrylate groups are linked, preferably via a spacer, which consists of 3 to 15 carbon atoms, preferably in particular 3 to 8 carbon atoms, in particular 3 carbon atoms, optionally further comprising not more than one divalent hydrocarbyl radical containing not more than three oxygen atoms, preferably not more than one oxygen atom, linked to the silicon atom.
[0055] In principle, the term "olefinically unsaturated radical" refers to all radicals that contain at least one double bond, regardless of whether the double bond is part of a functional group or otherwise expressed, for example, an acrylate or methacrylate group. In this context, acetylenically unsaturated radicals are radicals that contain a triple bond. Radicals that contain both double and triple bonds may be understood together by both terms and are included as well.
[0056] Y 1 If the radical is not a chemical bond, Y 1 The bridge Y is always bonded exclusively by Si-C bonds with silicon atoms which are bonded to each other by radicals. 1 Typical examples of radicals are linked organic units having 1 to 24 carbon atoms, preferably between 2 to 12 siloxanyl units. 1 is divalent, trivalent or tetravalent, in particular divalent. Y 1 The radical may be a bridging organic radical, including a polyarylene ether radical of formula (II) or (III).
[0057] Preferred bridging aromatic radicals Y 1 is of formula (VI): [ka] In the formula (VI), R 23 , R 24 , R 25 , R 26 , R 27 and R 28 The radical is a hydrogen radical or an optionally substituted hydrocarbyl radical or a radical of the formula OR 29 and R 29 is a hydrogen radical or a polyarylene ether radical of formula (II) or (III) or a hydrocarbyl radical which may contain an aliphatic or alicyclic heteroatom, the preferred heteroatom being an oxygen atom. It is possible for adjacent radicals in formula (VI) to be linked together to form cyclic radicals resulting in a fused ring system. In particular, R 23 , R 24 , R 25 , R 26 , R 27 and R 28 Any two radicals from the radical group are either a chemical bond or a divalent organic hydrocarbyl radical having 1 to 12 carbon atoms, preferably an aliphatic radical of the form -(CH2)3- having three carbon atoms linking the silicon atom with an aromatic ring.
[0058] Typical examples of such bridging aromatic radicals are the p-, m- or o-phenylene radical, the 2-methyl-1,4-phenylene radical, the 2-methoxy-1,4-phenylene radical, particularly preferred is the p-phenylene radical.
[0059] Two or more radicals of this type may be bonded to one another, so that, for example, there are two or more units of formula (VI) bonded to one another, and the oligomeric bridging unit may optionally be present through bonding of corresponding carbon atoms of the terminal aromatic rings to silicon atoms. The aromatic units may be bonded to one another directly or through bridging groups such as alkanediyl units, e.g., methylene, 1,2-ethanediyl, 1,1-ethanediyl, 2,2-dimethylpropyl or sulfone groups.
[0060] Further examples of aromatic bridging units are those in which two substituted phenol rings are bridged by an alkanediyl unit or other unit.
[0061] Typical representatives are the following radicals substituted on the phenolic oxygen or aromatic ring: 2,2-bis(4-hydroxyphenyl)propane radical (substituted bisphenol A radical), 2,2-bis(4-hydroxyphenyl)methane radical (substituted bisphenol F radical), bis(4-hydroxyphenyl)sulfone radical (bisphenol S radical), either the phenolic oxygen atom or the aromatic ring of the base skeleton is usually replaced by a radical of the -(C3H6)- type, which is linked to the silicon atom Si-C, resulting in crosslinking. The unsubstituted phenol group in the bisphenol base skeleton in such crosslinking units may be replaced by a radical of formula (II) or (III) during the synthesis of the polyorganosiloxane-polyarylene ether copolymer of the invention, resulting in the crosslinking Y 1 Even radicals can not only constitute a structural feature of the polyorganosiloxane backbone but can also contribute to the formation of the copolymers of the invention, or the structural groups which contain them as such, when they additionally contain the necessary minimum amount of crosslinkable unsaturated radicals, are already sufficient to form the polyorganosiloxane-polyarylene ether copolymers of the invention of formula (I).
[0062] Preferred Y is not bridged by aromatic units 1The radicals are alkanediyl, alkenediyl and alkynediyl which may contain heteroatoms and optionally aromatic groups as substituents, but which do not play a role or contribute to bridging in these radicals.
[0063] Typical examples are the methylene radical, the methine radical, the tetravalent carbon, the 1,1-ethanediyl and 1,2-ethanediyl groups, the 1,4-butanediyl and 1,3-butanediyl groups, the 1,5-pentanediyl, 1,6-hexanediyl, 1,7-heptanediyl, 1,8-octanediyl, 1,9-nonanediyl, 1,10-decanediyl, 1,11-undecanediyl and 1,12-dodecanediyl groups, the 1,2-diphenylethanediyl group, the 1,2-phenylethanediyl group, the 1,2-cyclohexylethanediyl group. When the linear bridging units have more than one carbon atom and this is permitted by the substitution pattern, each of these groups may have other connectivity, i.e., the use of different chain atoms apart from the result of α,ω connectivity, i.e., crosslinking by the first and last atoms of each of the linear units. Moreover, typical examples are not only the linear representatives of the bridged hydrocarbons mentioned, but also their isomers, which in turn may have crosslinking bonds with silicon atoms by bridging different carbon atoms of the hydrocarbon structure.
[0064] Examples of particularly preferred radicals from the group of hydrocarbyl radicals containing no non-aromatic heteroatoms are -CH2CH2-, -CH(CH3)-, -CH=CH-, -C(=CH2)- and -C≡C-.
[0065] Typical fluorine-substituted bridge Y 1 Examples of radicals are -C(CF3)2-, -C(H)FC(H)F- and -C(F2)-C(F2)- radicals.
[0066] Examples of typical heteroatom-containing bridging radicals are, for example, ethyleneoxypropylene and ethyleneoxybutylene radicals. Further typical examples are those with both -(CH2) n - or -CH2-CH(R30 )-C(=O)O- radical, n is usually 3 to 8, R 30 is a hydrogen atom or a methyl group, and a glycol radical or a phenylene ether radical bonded to the silicon atom by its terminal group.
[0067] Y 1 A further typical example of a radical is a chemical bond directly connecting two silicon atoms to each other.
[0068] R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13 Radicals and R 23 , R 24 , R 25 , R 26 , R 27 and R 28 Typical examples of radicals are the hydrogen radical, saturated hydrocarbyl radicals such as methyl, ethyl, n-propyl, isopropyl, primary, secondary and tertiary butyl radicals, aromatic radicals such as hydroxyethyl, phenylethyl, phenyl, benzyl, methylphenyl, dimethylphenyl, ethylphenyl, heteroatom-containing radicals such as hydroxymethyl, carboxyethyl, methoxycarbonylethyl and cyanoethyl radicals, and acrylate and methacrylate radicals such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, t-butyl acrylate, t-butyl methacrylate, 2-ethylhexyl acrylate and norbornyl acrylate, olefinically or acetylenically unsaturated hydrocarbyl radicals.
[0069] If desired, adjacent radicals may be joined to each other to form similar cyclic saturated or unsaturated radicals, resulting in fused polycyclic structures. 4 , R 5 , R 6 , R 7 , R 8 , R 23 , R 24 , R 25 , R 26 , R 27 and R 28 Mention has been made of the possibility that a particular radical from the radical group may be a chemical bond or a divalent hydrocarbyl radical.
[0070] The index h in formula (II) is 0, and R 13 is a hydrogen radical, the radical of formula (II) is a substituted or unsubstituted phenol radical. Typical examples of such phenol radicals of formula (II) are the phenol radical, ortho-, meta- or para-cresol radical, 2,6-, 2,5-, 2,4- or 3,5-dimethylphenol radical, 2-methyl-6-phenylphenol radical, 2,6-diphenylphenol radical, 2,6-diethylphenol radical, 2-methyl-6-ethylphenol radical, 2,3,5-, 2,3,6- or 2,4,6-trimethylphenol radical, 3-methyl-6-tert-butylphenol radical, thymol radical, 2-methyl-6-allylphenol radical and 4-allyl-2-methoxyphenol (=eugenol) radical, which may be substituted on the oxygen atom and may be linked to the polyorganosiloxane backbone by a direct bond of the aromatic ring carbon atom or by a C3 spacer of -(CH2)3-.
[0071] The entire list of examples of typical radicals is illustrative but should be understood to be in no way limiting.
[0072] The polyorganosiloxane-polyarylene ether copolymer of formula (I) is preferably used as a binder for the production of metal-plated laminates. The polyorganosiloxane-polyarylene ether copolymer of formula (I) is crosslinked in the production of the laminate. The laminate is preferably a metal foil clad laminate. The laminate is preferably used in electronic components, preferably in high frequency applications, very particularly those operating at frequencies above 1 GHz.
[0073] Surprisingly, it has been found that polyorganosiloxane-polyarylene ether copolymers of formula (I) having unsaturated organic functional groups appropriate for the purpose or formulation are particularly suitable.
[0074] The polyorganosiloxane-polyarylene ether copolymer of formula (I) has a dielectric loss factor of less than or equal to 0.0040 at 10 GHz.
[0075] In the context of the present invention, the polyorganosiloxane-polyarylene ether copolymers of formula (I) also include in particular the preferred structures of formulae (Ia), (Ib), (Ic) and (Id): [O 3-a / 2 R a Si-Y 1 (SiR a O 3-a / 2 ) b ] c (R 3 3SiO 1 / 2 ) f (Ia), [O 3-a / 2 RaSi-Y 1 (SiRaO 3-a / 2 ) b ]c(R 1 SiO 3 / 2 ) d (R 3 3SiO 1 / 2 ) (Ib), (R 1 SiO 3 / 2 ) d (R 3 3SiO 1 / 2 ) f (I C), (R 1SiO 3 / 2 ) d (Id).
[0076] These are particularly suitable for carrying out the present invention. 2 2SiO 2 / 2 ) e These units are the main, but not the only, components of polyorganosiloxanes according to the prior art up to now. This structurally particularly defines the characteristics of the present invention from the known prior art.
[0077] In particularly preferred embodiments of (Ia) and (Ib), values of a = 2 and b = 1. All definitions of the radicals and indices of formulae (Ia), (Ib), (Ic) and (Id) are the same as already stated above.
[0078] The polyorganosiloxane-polyarylene ether copolymer of the present invention of formula (I) can be prepared preferably from a hydroxyaryl-functional polyorganosiloxane compound of formula (VII) by reacting the aryl hydroxy radicals of the polyorganosiloxane compound of formula (VII). [O 3-a / 2 R 31 a Si-Y 2 (SiR 31 a O 3-a / 2 ) b ] c (R 32 SiO 3 / 2 ) d (R 33 2SiO 2 / 2 ) e (R 34 3SiO 1 / 2 ) f (SiO 4 / 2 ) g (VII) (In the formula (VII), R 31 is an R radical, and R 32 is R 1 Radical, R 33 is R 2 Radical, R 34 is R3 Radical and Y 2 is Y 1 The radical, the difference is that R 31 , R 32 , R 33 Or R 34 is a radical of formula (II) or Y 2 comprises such a radical of formula (II), in this radical of formula (II) the index h is always 0 and R 13 The radical is always a hydrogen radical, and R 31 , R 32 , R 33 and R 34 cannot be a polyarylene ether radical of formula (III), and Y 2 cannot contain a radical of formula (III), However, at least 1 mol% of all Si-bonded radicals are in the state of h = 0 and R 13 = hydrogen, a radical of formula (II) with a phenol of formula (VIIIa) or (VIIIb) [ka] (In the above (VIIIa) and (VIIIb), R 9 , R 10 , R 11 , R 12 and R 14 The radicals and j have the definitions given above. or by oxidative coupling of a mixture of (VIIIa) and (VIIIb).
[0079] In the above method, h=0 and R 13 The radicals of formula (II) where h=hydrogen must be present in sufficient amounts in the polyorganosiloxane of formula (VII) so that there is sufficient co-reactant available for the phenol of formula (VIII) to produce the inventive copolymer of formula (I). This means that at least 1 mol %, and preferably at least 2 mol %, of the total Si-bonded radicals have h=0 and R 13= hydrogen. This is therefore a prerequisite for the polyorganosiloxanes of formula (VII).
[0080] The phenols for oxidative coupling with the polyorganosiloxanes of formula (VII) are those of formula (VIIIa) to generate the radicals of formula (II).
[0081] The phenols for oxidative coupling with the polyorganosiloxanes of formula (VII) are bisphenols of formula (VIIIb) to generate radicals of formula (III).
[0082] j is preferably 0 or 1, in particular 1.
[0083] Depending on the latitude of the preparation process chosen for the olefinic and acetylenically unsaturated groups, these groups essential to the invention are introduced in a further process step after copolymerization. How this is possible and the options available for the selection of only limitedly hydrosilylatable olefinic and acetylenic groups in the preparation of the inventive copolymers of formula (I) will become clear below.
[0084] Oxidative coupling is known per se. The method of oxidative copolymerization of phenols to prepare polyphenylene ethers is described by way of example in US Pat. No. 3,306,874, although this reference should be understood as merely illustrative and non-limiting, and other prior art suitable for the preparation of polyarylene ethers is meant to be relevant here as well. Further steps for subsequent functionalization are per se also prior art. However, they have not been described in combination, which means that the method described here is entirely novel. The fact that this novel combination of known methods solves a problem that has not been solved up to now is surprising. If this were obvious, the problem would have been solved well before, since the corresponding polymers for commercial purposes have already been the subject of research for more than 20 years, as shown in the discussion of the prior art.
[0085] The viscosity of the polyorganosiloxane compounds of formula (VII) can vary over a wide range depending on the average number of structural units per molecule from which they are formed, or they may be solid.
[0086] The liquid organopolysiloxane compound of formula (VII) in a non-crosslinked state at 25° C. preferably has a viscosity of 20 to 8,000,000 mPa, more preferably 20 to 5,000,000 mPa, and particularly 20 to 3,000,000 mPa.
[0087] The solid organopolysiloxane compound of formula (VII) in a non-crosslinked state preferably has a glass transition temperature in the range of 25°C to 250°C, more preferably 30°C to 230°C, and particularly preferably 30°C to 200°C.
[0088] The organopolysiloxane compounds of formula (VII) may be prepared by any method. The preferred method for preparing these compounds is the hydrolysis and co-condensation of a compound of general formula (IX) with a compound of formula (X): Hal 3-a R 31 a Si-Y2 (SiR 31 a Hal 3-a ) b (IX) R 36 m SiHal 4-m (X) In the above formula, Hal is a hydrolyzable group, R 31 and Y 2 has the definition already given above, m is an integer ranging from 0 to 3; R 31 When m=1, R 1 radical, where m=2, R 2 radical, where m=3, R 3 Radical, a and b have the definitions already given for formula (VII).
[0089] Compounds (IX) are obtained by conventional methods, the type of reaction used being highly dependent on the composition of the respective compound (IX).Typically, compounds (IX) are obtained, for example, by hydrosilylation from olefinically unsaturated organic precursors, for example acetylene, diallyl or divinyl compounds, and Si-H functional silicone units.
[0090] Grignard reaction from halogenated organic precursor and subsequent reaction with halogenated or alkoxylated organic silanes are also methods envisaged herein.If necessary, it is also possible to use metal halide exchange reaction of halogenated organic precursor with alkali metal alkyl compound, for example butyl lithium, and further reaction known for bonding with silicone unit.Those skilled in the art are aware of such methods and can easily utilize and understand them from available literature.Since these methods are not the subject of the present invention, in this respect, only reference is made to literature and searchable prior art.
[0091] The relative proportions of compounds of formula (IX) that are co-condensed with compounds of formula (X) are defined by the values of the indices c, d, e, f and g in formula (VII).
[0092] Hal is preferably a halogen, acid or alkoxy group, more preferably a chloride, acetate, formate, methoxy or ethoxy group.
[0093] The organosiloxanes thus obtained can be modified, if desired, and further modified by further reactions, e.g., equilibration, so that by use of methods known in the art for preparing virtually any branched siloxane oligomers and polymers and silicone resins, all of which are considered to be encompassed by the term "organopolysiloxane" in the context of the present invention.
[0094] The cohydration is preferably carried out in such a way that a mixture of compounds (IX) and (X), optionally with a preferred aromatic solvent, is metered into water or dilute acid while cooling. In the case of gaseous acids such as HCl, metering into concentrated aqueous HCl is also advisable, if the acid released is collected in gas form. Depending on the nature of the Hal group, the hydrolysis is more or less exothermic, so that cooling is necessary both for the safe running of the reaction and possibly for the avoidance of side reactions in the corresponding synthesis sequence. In contrast, it may be advantageous and necessary to use high temperatures to complete the reaction.
[0095] The reaction times are generally very short for chlorosilanes, so that the time required to carry out the process in batch operation depends mainly on the cooling output. Alternatively, the cohydrolysis of (XI) and (XII) can also be carried out in a continuous manner, possible options for this being loop and also column reactors and tubular reactors.
[0096] For depletion of residual acid, excellent washing with water under reduced pressure, clean phase separation and purification of the hydrolysis product are advantageous.
[0097] The above process can be carried out under standard pressure, however, depending on the purpose, it can be carried out at higher or lower pressure as well.
[0098] Formula (R 3 3SiO 1 / 2 ) f As a result of the use of groups of formula (R), it is necessarily possible both to control the molecular weight and to reduce the level of alkoxy and silanol groups during the synthesis. If the synthesis is carried out by the hydrolysis method, the latter are generated during the synthesis, which is the preferred embodiment. 3 3SiO 1 / 2 ) f When the groups are produced using chlorosilane precursors, symmetrical disiloxanes are also produced from them in the course of the synthesis, but these can be cleaved again under acid hydrolysis conditions and are therefore still available as end groups for reaction with silanol groups, as starting materials are produced on the organopolysiloxanes produced after hydrolysis of the chlorosilanes. Thus, the silanol groups are reduced. Alkoxy groups, especially those with small alkyl radicals, also produce silanol groups under conditions of acid hydrolysis by removing short-chain alcohols, and alkoxy groups are also reduced by additional use of terminal structural groups. Any remaining disiloxanes, especially those exclusively or predominantly replaced by short-chain alkyl radicals, especially methyl radicals, can generally be distilled off after the end of the synthesis, so that it is also possible to use them in excess.
[0099] The chlorosilanes or disiloxanes which generate these end groups can also be added separately to the synthesis in the final step, and the reduction of silanol groups can be brought about in a controlled manner by acidic hydrolysis conditions. It is advantageous here to always use an excess of the terminal chlorosilane and to remove the disiloxanes generated by distillation. It is particularly advantageous to use vinyldimethylchlorosilane, dimethylchlorosilane or trimethylchlorosilane for this purpose, since the disiloxanes generated therefrom can be particularly easily removed by distillation. Alternatively, it is of course also possible to immediately use the disiloxane and to select the hydrolysis conditions, in which case it is necessary to add a sufficient amount of catalytic acid, preferably hydrochloric acid. Typically, in this case, 50 to 1000 ppm of hydrochloric acid is used, relative to the amount of siloxane in the reaction mixture.
[0100] Functional groups not tolerated by the reaction forming polyorganosiloxane (VII) may then be introduced into the polyorganosiloxane structure, for example by hydrosilylation. Thus, for example, it is possible to introduce the 4-allyl-2-methoxyphenol (eugenol) functionality or the 2-allylphenol functionality as typical examples of the hydroxyaryl radicals essential in (VII).
[0101] It is especially necessary that there is a sufficient amount of olefinically unsaturated groups in the copolymer of formula (I) when using hydrosilylation reactions that consume olefinic groups, since it is a requirement for the copolymers of the present invention that they are free radically crosslinkable when used with appropriate olefinically unsaturated groups. The easiest way to achieve this is by adjusting the stoichiometry between the olefinically unsaturated groups and the Si-H groups, which means using an appropriate excess of olefinic groups. If only one type of olefinic group is used, the olefinic group that is sterically easiest to access will react first, and the olefinic group that is more difficult to access will remain for later free radical curing. This leads to disadvantages in random copolymers as well as possibly free radical curing, such as lower reaction rates or more incomplete reactions. To compensate for this, it is possible, for example, to use two different types of olefinically unsaturated groups that are hydrosilylated at different rates, for example allyl or vinyl groups as examples of rapidly hydrosilylatable groups combined with acrylate or methacrylate groups as examples of olefinically unsaturated groups that are not easily hydrosilylatable. Thus, hydrosilylation will proceed primarily or exclusively to the more rapidly hydrosilylatable groups, and the less rapidly hydrosilylatable groups will remain in greater abundance for subsequent free radical curing, which can affect molecular architecture and reaction kinetics.
[0102] In principle, the subsequent introduction of the hydrosilylatable or free radical curable groups required for the copolymer of formula (I) is possible by known methods of organic chemistry, either functionalization of the polyarylene ether moiety or the polysiloxane moiety or both of these components to produce the copolymer of formula (I). Thus, the hydrosilylatable groups in the polyarylene ether units can be introduced, for example, on their optionally terminal phenolic OH groups. Reference is made generally to the chemistry of phenols herein, and as an example, an allyl group can be introduced to produce an allyl phenyl ether group, which can then be converted to allylphenol by a subsequent Claisen rearrangement. Since it is possible to use publicly accepted knowledge herein, the synthetic routes to the raw materials used herein are known to those skilled in the art and will not be further detailed at this point. In addition, it should be pointed out that the structural groups that can be used for the polyarylene ether units can also be natural substances, such as eugenol (4-allyl-2-methoxyphenol), in order to introduce the appropriate olefinically unsaturated groups into the polyarylene ether radicals as required.
[0103] As an example, reference is also made herein to the introduction of an acrylate group by reacting a phenolic OH group with 3-chloropropionyl chloride to give a 3-chloropropionic acid ester, followed by elimination of HCl from the chloropropyl radical, for example by addition of a trialkylamine to the reaction mixture, to generate an acrylate group by establishment of a double bond, since the acrylate group is the relevant free radically curable group. This reaction sequence is also described in the literature and is therefore known to the skilled person.
[0104] As a further example, the introduction of an olefinic group by subsequent silylation with an olefinically unsaturated chlorosilane or an olefinically unsaturated disiloxane is disclosed below as a further option.
[0105] A further method to ensure that a sufficient number of olefinically unsaturated free radically curable functional groups are present in the copolymer of formula (I) is to subsequently functionalize formula (VII) by proceeding in the same manner as already described above for the control of the molecular weight of polyorganosiloxane (VII) after oxidative coupling when combined with formulas (VIIIa) and (VIIIb). 3 where R 3 3SiO 1 / 2 ) f to the copolymer obtained initially after oxidative coupling or hydrosilylation, the precursors used for this process step in particular contain at least one R 3 The radical is in each case meant to be an olefinically unsaturated group, such as a vinyl group.
[0106] This is possible both by the hydrolysis method described above, and by the anhydrous method.
[0107] Formula (R 3 3SiO 1 / 2 ) f are produced under hydrolysis conditions by use of chlorosilane precursors of formula (X), symmetrical disiloxanes are also produced therefrom in the course of the synthesis, which are again cleavable under acidic hydrolysis conditions and are therefore further available as end groups for reaction with silanol groups and silicon-bonded alkoxy groups or else carbinol groups, which are formed on the organopolysiloxanes when prepared by the hydrolysis method and the carbinol groups may be present as phenolic OH groups.
[0108] In this specification, in particular in the case where certain methyl radicals are exclusively or predominantly substituted with short chain alkyl radicals, any remaining disiloxanes can generally be distilled off after completion of the synthesis, and therefore the formula (R 3 3SiO 1 / 2 ) f It is also possible to use an excess of the chlorosilane precursor for the group.
[0109] The chlorosilanes or disiloxanes which generate these end groups can also be added separately in the final synthesis step, and the reduction of silanol groups can be brought about in a controlled manner by acidic hydrolysis conditions. It is advantageous here to always use an excess of the end chlorosilanes and to remove the disiloxanes generated by distillation. It is particularly advantageous for this purpose to use vinyldimethylchlorosilane, divinylmethyl-chlorosilane, trivinylchlorosilane, methacryloyloxypropyl-dimethylchlorosilane, bismethacryloyloxypropylmethylchlorosilane, trismethacryloyloxypropylchlorosilane, acryloyloxypropyldimethylchlorosilane, bismethacryloyloxypropylmethyl-chlorosilane, trismethacryloyloxypropylchlorosilane. Alternatively, it is of course also possible to immediately use the disiloxanes and to select the hydrolysis conditions, in which case it is necessary to add a sufficient amount of catalytic acid, preferably hydrochloric acid. Typically in this case, 50 to 1000 ppm of hydrochloric acid is used relative to the amount of siloxane in the reaction mixture.
[0110] The final step can also be carried out under anhydrous conditions by adding the selected chlorosilane (preferably vinyldimethylchlorosilane, divinylmethylchlorosilane, trivinylchlorosilane, methacryloyloxypropyldimethylchlorosilane, bismethacryloyloxypropylmethylchlorosilane, trismethacryloyloxypropylchlorosilane, acryloyloxypropyl-dimethylchlorosilane, bismethacryloyloxypropylmethylchlorosilane or trismethacryloyloxypropylchlorosilane) from the oxidative coupling of (VII) with (VIIIa) or (VIIIb) to the copolymer dissolved in an inert organic solvent, and carrying out the reaction anhydrous in the presence of an auxiliary base, the auxiliary base used being preferably a basic metal salt and a nitrogen compound.
[0111] Suitable auxiliary bases used to capture the hydrogen halide produced are basic salts or nitrogen compounds such as amines, ureas, guanidines and amides. Examples of basic salts are sodium hydride, sodium amide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, calcium carbonate, calcium bicarbonate, calcium oxide, magnesium oxide, magnesium carbonate. Examples of nitrogen compounds are ammonia, ethylamine, butylamine, triethylamine, trimethylamine, tributylamine, N,N-dimethyldecylamine, triisooctylamine, urea, tetramethylurea, guanidine, tetramethylguanidine, N-methylimidazole, N-ethylimidazole, piperidine, pyridine, picoline, N-methylmorpholine. The amine compounds used are preferably those in which the nitrogen atom does not have a hydrogen atom.
[0112] Auxiliary base is preferably used in at least an equimolar amount relative to the halosilane. For each molar equivalent of halosilane, preferably at least 0.5 equivalents of base, more preferably at least 1.0 equivalents of base, in particular at least 2.0 equivalents of base. It is also possible to use a larger amount of auxiliary base, for example when it is fed simultaneously with the solvent. However, this usually does not bring any advantage and reduces the space-time yield and therefore the economic viability of the process. The halosilane is preferably added to the anhydrous reaction mixture from the first step of the process, and then the auxiliary base is metered in. This procedure can also be carried out in reverse, if necessary, so that auxiliary base is added to the reaction mixture from the first synthesis step, and then the halosilane is metered in.
[0113] It is also possible to use a mixture of two or more auxiliary bases.
[0114] The reaction of silanol radicals of polyorganosiloxane species or phenolic OH radicals of the copolymer from the oxidative coupling of (VII) with (VIIIa) or (VIIIb) with halosilanes of formula (XII) is preferably carried out at a temperature of at least -20°C, more preferably at least 0°C and in particular at least 10°C. The maximum permissible temperature additionally results from the boiling points of the solvent used and of the halosilanes of formula (X), the reaction temperature preferably does not exceed 200°C, more preferably 175°C and in particular 150°C.
[0115] The reaction mixture can be cooled or heated as required; it is possible to pre-adjust the individual reactants to a temperature before reacting with each other, for example, to utilize the heat of reaction. The process can be carried out either batchwise in a stirred reactor or continuously in a column reactor, loop reactor, fluidized bed reactor or tubular reactor. Any low molecular weight siloxanes produced in the reaction can be separated by distillation from the reaction mixture as required. The halide salts produced in the reaction can be decanted off, filtered off or centrifuged off, or dissolved in water and separated. For the subsequent aqueous workup, it is possible to adjust the amount of solvent already present or add additional solvents with a minimum solubility or miscibility with water, in particular a maximum of 5% by weight at 25° C., as required, for example to promote phase separation by establishing density differences.
[0116] Any excess of halosilane of formula (X) present is optionally removed by distillation prior to the aqueous workup.
[0117] Suitable aprotic solvents are aromatic hydrocarbon solvents, such as benzene, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene or mixtures thereof. The suitability of the solvent is determined by its ability to dissolve the copolymer of formula (I) to be produced. The solvent must be able to sufficiently dissolve the copolymer of formula (I) to be produced, and must not be miscible with water, i.e., it must not be able to dissolve more than 5% by weight of water itself, and must not participate in the reaction.
[0118] It may be necessary to determine the suitability of the solvent by appropriate experimentation. Aromatic solvents best satisfy the stated conditions and are therefore preferred.
[0119] The copolymers of formula (I) are chemically curable, and can be cured by chemical reaction to obtain a crosslinked insoluble network. The curing is carried out by the olefinic unsaturated groups mentioned above. Possible chemical crosslinking reactions include reactions known from the prior art, in particular free radical crosslinking, which can be initiated either by using a suitable radiation source, such as UV light, or by unstable chemical compounds that decompose into free radicals, and addition crosslinking, for example by hydrosilylation of olefinic unsaturated groups with Si-H functionality in the presence of a suitable hydrosilylation catalyst.
[0120] In order to achieve sufficient curing, a sufficient amount of functional groups must be present. Depending on the polyorganosiloxane molecule used according to the invention, there must be at least an average of 1.0 functional groups per polyorganosiloxane molecule according to the invention; preferably at least an average of 1.1, in particular at least an average of 1.2 functional groups in order to achieve sufficient curing. The functional groups here may be different, so that, for example, one part of the functional groups is a Si-H group and another part of the functional groups is a free radical curable or hydrosilylatable olefinically unsaturated group. It should be noted here that, according to the invention, there must always be a minimum proportion of olefinic or acetylenically unsaturated groups. If only one type of functional group is present, for example a single olefinic or acetylenically unsaturated functional group that is free radical curable, then the corresponding number of these functional groups must be present. For the purpose of copolymerization to obtain a homogeneous matrix, it must be ensured that the copolymerizability of the selected olefin and acetylenic groups is sufficient. Combinations of olefinic groups that are not copolymerizable with one another are also possible, provided that the resulting matrix of two or, if desired, more individual polymers remain compatible with one another and do not produce separate phases that separate one from the other into distinguishable domains. In this specification, each of the individual polymers itself is chemically hardenable, so that it must be ensured that the entire resulting matrix is chemically hardened after crosslinking.
[0121] Examples of suitable initiators herein, particularly for initiating free radical polymerization, include di-tert-butyl peroxide, dilauryl peroxide, dibenzoyl peroxide, dicumyl peroxide, cumyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-amyl peroxypivalate, tert-butyl peroxypivalate, tert-butyl peroxyisobutyrate, tert-butylperoxy-3,5,5-trimethylhexanoate, tert-butylcumyl peroxide, tert-butylperoxyacetate, tert-butylperoxybenzoate, 1,2,-di-tert-butylperoxycyclohexane, 2,2-di(tert-butylperoxy)butane, bis(4-tert-butyl-cyclohexyl)peroxydicarbonate, hexamethylperoxy, tert-butylperoxy-1,2,3,4-trimethyl ... Decyl peroxydicarbonate, tetradecyl peroxydicarbonate, dibenzyl peroxydicarbonate, diisopropylbenzene dihydroperoxide, [1,3-phenylenebis(1-methylethylidene)]bis[tert-butyl]peroxide, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, dicetyl peroxydicarbonate, acetylacetone peroxide, acetylcyclohexane-sulfonyl peroxide, tert-amylperoxy-2-ethylhexyl carbonate, tert-amylperoxyisopropyl carbonate, tert-amylperoxyneodecanoate, tert-amylperoxy-3,5,5-trimethylhexanoate, tert-butyl monoperoxymaleate, this list is merely illustrative and non-limiting. If necessary, it is also possible to use a mixture of different initiators for free radical reaction. The suitability of an initiator or a mixture of initiators for a free radical reaction depends on its decomposition kinetics and the requirements to be met. Taking these boundary conditions into due consideration, a person skilled in the art will be successful in selecting a suitable initiator.
[0122] In the case of formulations which contain not only olefinically and acetylenically unsaturated groups but also silicon-bonded hydrogen, they may cure via a hydrosilylation reaction. Suitable catalysts for the promotion of the hydrosilylation reaction are those known from the prior art.
[0123] Examples of such catalysts are compounds or complexes from the transition metal group comprising platinum, ruthenium, irridium, rhodium and palladium, preferably metal catalysts from the group of platinum metals or compounds and complexes from the group of platinum metals. Examples of such catalysts are metallic platinum and particulate platinum, which may be present on supports such as silicon dioxide, aluminum oxide or activated carbon, platinum halides, for example platinum compounds or complexes such as PtCl4, H2PtCl6·6H2O, Na2PtCl4·4H2O, platinum-olefin complexes, platinum-alcohol complexes, platinum alkoxide complexes, platinum-ether complexes, platinum-aldehyde complexes, platinum-ketone complexes including the reaction product of H2PtCl4·6H2O with cyclohexanone, platinum-1,3-divinyl-1,1,3,3-tetramethyldisiloxane with or without detectable content of inorganically bound halogen. Platinum-vinylsiloxane complexes such as platinum, bis(γ-picoline)platinum chloride, trimethylenedipyridine platinum chloride, dicyclopentadiene platinum dichloride, dimethylsulfoxy-ethenyl platinum(II) dichloride, cyclooctadiene platinum dichloride, norbornadiene platinum dichloride, γ-picoline platinum dichloride, cyclopentadiene platinum dichloride, and reaction products of platinum tetrachloride with olefins and primary or secondary amines or primary and secondary amines, such as reaction products of platinum tetrachloride dissolved in 1-octene with sec-butylamine or ammonium-platinum complexes. In a further embodiment of the method of the present invention, complexes of iridium with cyclooctadienes, such as μ-dichlorobis(cyclooctadiene)-diiridium(I), are used.
[0124] This list is merely illustrative and non-limiting: hydrosilylation catalyst development is a dynamic field of research that is constantly discovering new active species that can of course be used herein as well.
[0125] The hydrosilylation catalyst preferably comprises a platinum compound or complex, preferably platinous chloride and platinum complexes, especially platinum-olefin complexes, more preferably platinum-divinyltetramethyldisiloxane complexes.
[0126] In the method of the present invention, the hydrosilylation catalyst is used in an amount of 2 to 250 ppm by weight, preferably 3 to 150 ppm by weight, and particularly preferably 3 to 50 ppm by weight, based on the total composition.
[0127] In a preferred embodiment, the copolymer of formula (I) is applied to a metal substrate.
[0128] The copolymers of formula (I) are particularly suitable for use as binders and / or adhesion promoters in the manufacture of metal plated laminates, especially for electronic applications, especially metal foil clad laminates, especially for use in high frequency applications, very especially those operating at frequencies above 1 GHz.Particularly preferred is the use of metal foil clad electrolaminates, which are used for the manufacture of printed circuit boards in electronic devices, especially for high frequency applications.
[0129] The metal foil clad electrolaminates may, but do not necessarily, comprise a reinforcing material. This means that they may, for example, comprise a reinforcing fabric, such as a woven or nonwoven fiber fabric. When present, the reinforcing material is preferably arranged in a layer. Herein, the reinforcing layer may be produced from a number of different fibers.
[0130] Such a reinforcing layer helps to control shrinkage properties and improve mechanical strength.
[0131] If a reinforcing layer is included, the fibers forming this layer may be selected from a number of different options. Non-limiting examples of such fibers are glass fibers, such as E-glass, S-glass and D-glass fibers, silica fibers, polymer fibers, such as polyetherimide fibers, polysulfone fibers, polyetherketone fibers, polyester fibers, polycarbonate fibers, aromatic polyamide fibers or liquid crystal fibers. The fibers may have a diameter of 10 nm to 10 μm. The reinforcing layer has a thickness of 200 μm or less, preferably 150 μm or less.
[0132] A preferred embodiment is the use of the copolymer of formula (I) as a binder or co-binder together with an organic binder for the production of metal foil clad laminates of glass fiber composites for the further production of printed circuit boards. The preferred metal is copper.
[0133] For the present invention use of copolymers of formula (I), they may be used as the sole binder.They may also be used in combination with polyorganosiloxanes, organic monomers, oligomers and polymers.The organic monomers, oligomers and polymers commonly used for this purpose include polyphenylene ethers, bismaleimides, bismaleimide-triazine copolymers, hydrocarbon resins, both aliphatic hydrocarbon resins, such as polybutadiene, and aromatic hydrocarbon resins, such as polystyrene, as well as hybrid systems with both aliphatic and aromatic properties, such as styrene-polyolefin copolymers, epoxy resins, cyanate ester resins, and others, whose selection should probably be considered as illustrative and non-limiting, again with no fundamental restrictions on the type of copolymer.
[0134] Preferred organic monomers, oligomers and polymers are oligomeric and polymeric polyphenylene ethers, monomeric, oligomeric and polymeric bismaleimides, oligomeric and polymeric hydrocarbon resins and bismaleimide-triazine copolymers. Herein it is possible to use organic monomers, oligomers and polymers in mixtures with one another, if desired.
[0135] The proportion of organic monomers, oligomers and polymers in the blend containing the copolymer of formula (I), when an organic component is contained, is 10% to 90%, preferably 20 to 90%, particularly preferably 30 to 80%, based on the mixture of the copolymer of formula (I) and the organic monomers, oligomers and polymers taken as 100%.
[0136] In addition, the mixture of the copolymer of formula (I) with organic monomers, oligomers or polymers thereof may, if necessary, be dissolved in further organic monomers having olefinic or acetylenically unsaturated groups as reactive diluents, such as styrene, α-methylstyrene, para-methylstyrene and vinylstyrene, chloro- and bromostyrene.
[0137] Typical non-reactive solvents for dissolving the copolymer of formula (I) and its mixtures with organic monomers, oligomers and polymers include, for example, aliphatic mixtures having a particular boiling range, aliphatic or aromatic solvents such as toluene, xylene, ethylbenzene or mixtures of the same aromatic compounds, ketones such as acetone, methyl ethyl ketone, cyclohexanone, carboxylic acid esters such as ethyl acetate, methyl acetate, ethyl formate, methyl formate, methyl propionate, ethyl propionate, etc. In particular, excellent solubility of mixtures of polyorganosiloxanes of formula (I) with organic monomers, oligomers and polymers is most likely to be achieved in aromatic solvents such as toluene, xylene, ethylbenzene and mixtures thereof.
[0138] When polyorganosiloxane is used as further mixture component together with copolymer of formula (I) and optionally further organic monomers, oligomers or polymers, it is essential to select polyorganosiloxane that is compatible with selected organic components and does not cause phase separation.In these cases, generally, phenyl-rich polyorganosiloxane should be used, since phenyl group improves compatibility with organic components.Aromatic-rich polyorganosiloxane should be used in particular together with organic polymers relatively rich in aromatics, such as polyphenylene ethers or aromatic hydrocarbon resins, and both bridging aromatic groups and aromatic substituents that are terminally bonded with silyl units contribute to establish compatibility.
[0139] The exact amount of aromatic groups required to establish compatibility of the polyorganosiloxane with a particular selection of organic binder must be determined depending on the selection of organic binder.
[0140] In the same way that it is possible to mix two or more organic polymers, optionally selected from different polymer classes, and to use them in binder formulations, it is also possible to combine two or more polyorganosiloxanes with each other in binder formulations. Moreover, it is possible and within the scope of the present invention to mix two or more different copolymers of formula (I) with each other to obtain a binder. The mixture of polyorganosiloxane, copolymer of formula (I) and further organic polymers herein may be obtained from the reaction to produce the copolymer of formula (I), possibly in parallel with the polyarylene ether units not bonded to the polyorganosiloxane backbone from the polymerization of the polyarylene ether precursors (VIIIa) and (VIIIb) or the unhydrolyzed polyarylene ethers of formulas (Xa) and (Xb), if there are still unreacted polyorganosiloxane portions of formula (VII) or (IX) after the reaction is completed. Such mixtures and their use are within the scope of the present invention, however, they also include the copolymers of formula (I).
[0141] It is easy to determine the compatibility of one or more polyorganosiloxanes with one or more organic oligomers or polymers by mixing the polyorganosiloxanes and organic binders in a solvent that dissolves all the components, which is advantageously selected, then removing the solvent by conventional techniques, such as distillation or spray drying, and evaluating the resulting residue using visual or microscopic techniques, and, if necessary, electron microscopy. A compatible mixture can be separated from the organic component, and it is recognizable that there are non-silicon domains that are recognizable as a separate phase.
[0142] The use of further compounding components, such as additives, which may optionally include silanes, for example defoamers and degassing agents, wetting and dispersing agents, leveling agents, compatibilizers, adhesion promoters, curing initiators, catalysts, stabilizers, fillers including pigments, dyes, inhibitors, flame retardants, crosslinking coagents, etc., is within the scope of the present invention, and the choice of such components is essentially unlimited. Apart from compatibility testing for the purpose of suitable miscibility properties, it may also be necessary to test for compatibility in terms of reactivity, both to prevent premature gelation and to ensure that a sufficiently rapid polymerization or copolymerization of all components with each other is achieved during curing, as well as to test for sufficient wetting and possibly further properties. This should be noted and, if necessary, included within the scope of making the compound.
[0143] Examples of fillers that can be used are fillers such as silica, for example precipitated silica or fumed silica, which may be hydrophilic or hydrophobic, preferably hydrophilic, and may additionally be functionally and optionally reactively modified with organic groups on its surface, quartz, which may be surface treated or surface functionalized as required so that it can have reactive functional groups on its surface, aluminum oxide, aluminum hydroxide, calcium carbonate, talc, mica, clay, kaolin, magnesium sulfate, carbon black, titanium dioxide, zinc oxide, antimony trioxide, barium titanate, strontium titanate, corundum, wollastonite, zirconium tungstate, ceramic hollow beads, aluminum nitride, silicon carbide, barium oxide, magnesium oxide, magnesium hydroxide, solid glass beads, hollow glass beads and boron nitride. Further fillers that can be used are core-shell particles of various materials, for example surface-silica-coated silicone resin beads, polymer-coated elastomer particles, said elastomer particles may be silicone elastomers as required, a typical example of the surface coating of such elastomer particles is a polymethyl methacrylate shell. The ceramic filler preferably has a D of 0.1 μm to 10 μm. 90 The particle size is expressed as a value. The filler is preferably present in an amount of 0.1 to 60% by weight, preferably 0.5 to 60% by weight, in particular 1 to 60% by weight, based on the total binder formulation consisting of binder, reactive monomer, additives and filler as 100%. In other words, the amount of any non-reactive solvent used is not counted.
[0144] Among the fillers, particular emphasis is placed on those which are thermally conductive: these are aluminium nitride, boron nitride, silicon carbide, diamond, graphite, beryllium oxide, zinc oxide, zirconium silicate, magnesium oxide, silicon oxide and aluminium oxide.
[0145] In principle, the binder formulation may contain flame retardant additives, usually in an amount of 5-25% by weight. However, it is a feature of the copolymers of formula (I) that they reduce the need for flame retardant additives, since the polyorganosiloxane components in the copolymers of formula (I) themselves already exhibit flame retardancy. As can be noticed from the discussion of the prior art as background to the present invention, polysilsesquioxanes and siloxanes are known for their flame retardant properties. Their use as flame retardant additives alone is part of the prior art. It is therefore a particular advantage of the present invention that it is possible to combine herein the functionality of a binder suitable for high frequency applications with the functionality of flame retardancy. Thus, depending on the amount of polyorganosiloxane used in the copolymers of formula (I), it is possible to reduce the amount of flame retardant additives. In the case of an amount of at least 20% by weight, based on the total mixture of all binders and reactive organic monomers used, the amount of flame retardant additive is preferably only 0-10% by weight, more preferably 0-8% by weight and in particular 0-5% by weight, which means that when copolymers of formula (I) are used, depending on the choice of organopolysiloxane and the amount used, it is possible to dispense with the use of a flame retardant additive.
[0146] Typical examples of flame retardant additives are hydrates of metals Al, Mg, Ca, Fe, Zn, Ba, Cu or Ni and borates of Ba and Zn. Flame retardant additives may be surface-treated, in which case they may have reactive groups on the surface as required. Flame retardant additives may be halogenated organic flame retardant additives, such as hexachloroendomethylenetetrahydrophthalic acid, tetrabromophthalic acid or dibromoneopentyl glycol. Examples of further flame retardant additives are phosphorus-containing components such as melamine cyanurate, phosphinates, diphosphinates, phosphazenes, vinylphosphazenes, phosphonates, phosphaphenanthrene oxides, finely divided melamine polyphosphates, etc.
[0147] Further examples of brominated flame retardant additives are bispentabromophenylethane, ethylenebistetrabromophthalimide, tetradecabromodiphenoxybenzene, decabromodiphenyl oxide or brominated polysilsesquioxanes. Some flame retardant additives have synergistic effects. This is the case, for example, of the combination of halogenated flame retardant additives with antimony trioxide.
[0148] Further examples of other ingredients are antioxidants, stabilizers against deterioration by weathering, lubricants, plasticizers, colorants, phosphorescent agents or other agents for labelling and traceability purposes, as well as antistatic properties.
[0149] The copolymers of formula (I) are preferably crosslinked in the process of their use as binders or co-binders.
[0150] The crosslinking coagents used are in particular polyunsaturated free radically curable or hydrosilylatable monomers and oligomers, as illustrated in the following non-limiting examples: These include, for example, diolefinically unsaturated components, such as symmetrically olefinically unsaturated disubstituted disiloxanes, such as 1,1,3,3-tetramethyl-1,3-divinyldisiloxane, 1,1,3,3-tetramethyl-1,3-dipropylmethacryloyldisiloxane, diolefinically unsaturated disubstituted, such as diallyl-, divinyl-, diacryloyl- or dimethacryloyl-substituted, organic monomers or oligomers, such as conjugated and nonconjugated dienes, such as 1,9-decadiene, 1,3-butadiene, etc. These likewise include trifunctional olefinically unsaturated monomers or oligomers, such as 1,2,4-trivinylcyclohexane, triallyl cyanurates or triallyl isocyanurates, tri(meth)acrylates, for example trimethylolpropane trimethacrylate.
[0151] These likewise include trivalently unsaturated substituted monomers and oligomers, such as 2,4,6,8-tetramethyl-2,4,6,8-tetravinylcyclotetrasiloxane, 2,4,6,8-tetraphenyl-2,4,6,8-tetravinylcyclotetrasiloxane, 2,2-bis[[(2-methyl-1-oxoallyl)-oxy]methyl]-1,3-propanediylbismethacrylate (pentaerythritol tetramethacrylate), tetraallyl orthosilicate, cis,cis,cis,cis-1,2,3,4-cyclopentanetetracarboxylate tetraallyl, tetraallyl silanes, glyoxal bis(diallyl acetal).
[0152] Hydrosilylation curing is also envisaged, as is free radical curing, so that components containing polySi-H functionality can also function as crosslinkers, e.g., 1,1,3,3-tetramethyl-1,3-disiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, 1,4-bis(dimethylsilyl)benzene or chain-linked multiply linked Si-H functional and / or terminal Si-H functional oligo- and polyorganosiloxanes.
[0153] Useful catalysts or initiators for the free radical curing of the copolymer of formula (I) and the binder formulations made of polyorganosiloxanes, organic monomers, oligomers and polymers are the same as already mentioned above, in particular peroxides.In addition, suitable for the initiation of the free radical curing of both the copolymer of formula (I) itself and the binder formulations described are further free radical initiators, such as azo components, for example α,α'-azobis(isobutyronitrile), redox initiators, for example combinations of peroxides such as hydrogen peroxide and iron salts, or azides, such as acetyl azide.
[0154] For the application of the present invention, the copolymers of formula (I) or the formulations comprising them may be used solvent-free or as solvent-containing formulations. Generally, they are used as solvent-containing formulations in order to promote homogeneous mutual distribution of all the components of the formulation as well as wetting and impregnation of any reinforcing layers used. Generally, the reinforcing layers are used in the same way. Preferably, the reinforcing layers are glass fiber woven fabrics. The reinforcing layers can be impregnated by impregnation application of the formulations, where appropriate, various technical solutions are available, including continuous processes, the choice of which for the manufacture of the metal clad laminates of the present invention is in no way limited. Non-limiting examples of application techniques are dipping, spraying, flow coating, knife coating, etc. of the web of reinforcement by a roller system, where appropriate in a continuous process. It is an advantage of the present invention that all available techniques can be used without restriction and modification, and that no specific new process is required for the use of the copolymers of formula (I). In this respect, the present invention is entirely within the scope of the prior art available in the manufacture of metal clad laminates. What is novel is the use of the copolymers of formula (I) for the preparation of said metal-clad laminates, which has not been known up until now.
[0155] Impregnation is followed by a drying step to remove any solvent used. For the drying method, conventional techniques are also used. These include, in particular, thermally induced evaporation with or without vacuum. By suitable adjustment of the reactivity and tack of the binder mixture used under suitable conditions, for example cooling, what is obtained after this step is a storable composite that can be further processed at a later time if necessary. In the final step of the method, the binder formulation is polymerized again by conventional methods. Any initiators contained here for free radical polymerization are heated above their decomposition temperature, so that they decompose to generate radicals that initiate the free radical polymerization of the binder formulation. In principle, radiation curing methods can also be used.
[0156] When hydrosilylation curing is used rather than free radical polymerization, the temperature used in this step must be suitable for deactivating any inhibitors included with the hydrosilylation catalyst used and for releasing the catalytic activity of the hydrosilylation catalyst.
[0157] This step is generally carried out at elevated temperatures, preferably between 60 and 390°C, more preferably between 70 and 250°C, in particular between 80 and 200°C, the temperature being effective for a period of preferably between 5 and 180 minutes, more preferably between 5 and 150 minutes, in particular between 10 and 120 minutes. Furthermore, it is customary to use high pressure in this step. Customary pressures are in the range of 1 to 10 MPa, more preferably between 1 and 5 MPa, in particular between 1 and 3 MPa.
[0158] In this second step, the composite is laminated with a conductive metal layer, in which at least one layer of a selected metal is applied to one or both sides of the composite consisting of the reinforcing layer and the binder formulation before curing occurs. In other words, between the first step consisting of impregnation and drying and the second step comprising the chemical curing of the binder formulation, at least one conductive metal is laminated to the composite from the first step.
[0159] Useful conductive metals include in particular at least one from the following selection: copper, stainless steel, gold, aluminum, silver, zinc, tin, lead and transition metals. The thickness of the conductive layer and its shape, size or surface texture are basically not limited. The conductive metal layer preferably has a thickness of 3 to 300 μm, more preferably 3 to 250 μm, in particular 3 to 200 μm. The thicknesses of the two layers of at least one conductive metal may be different and do not have to be the same if two layers are used. It is particularly preferred that when the conductive metal is copper and two conductive layers of conductive metal are used, both layers are copper. The conductive metal is preferably used in the form of a foil of said metal. The arithmetic mean roughness Ra of the metal foil used is preferably 2 μm or less, more preferably 1 μm or less, in particular 0.7 μm or less. The lower the surface roughness, the better the suitability of the respective foil for use in high frequency applications, which is a preferred object of the present invention. To improve the adhesion between the conductive metal layer and the composite of the binder formulation and the reinforcing layer, various prior art methods can be used, if necessary, such as the use of an adhesion promoting layer, electrolytic deposition of a metal layer on the composite of the binder formulation and the reinforcing layer, or vapor deposition. The conductive metal layer can be directly on the composite of the binder formulation and the reinforcing layer or can be bonded to it by an adhesion promoting layer.
[0160] If no reinforcing layer is included, the layer of the binder formulation comprising the polyorganosiloxane of formula (I) is produced by depositing the layer of the binder formulation on a carrier, for example a separating film or a separating plate, and suitable materials for the carrier are those which, in principle, are either the binder formulation dried or hardened at a later time point again releasable, for example polytetrafluoroethylene, polyester and the like.Releasability and film-forming property on each carrier material should be determined individually depending on the binder composition.The remarks made regarding the method remain equally applicable to this unreinforced variant.
[0161] The reinforced or unreinforced composite from the first step and the laminated composite from the second step can be used to make a multi-layer structure in which two or more layers of the composite from the first step are stacked or, for example, instead are superimposed with the clad laminate from the second step, and the uncured composite from the first step is then cured in a manner that basically corresponds to the procedure for the production of metal clad laminates. For the production of thicker layers, it is also possible here to stack two or more layers of the reinforced or unreinforced composite from the first step directly in succession.
[0162] Apart from the production of metal clad laminates, in particular electrolaminates, the copolymers of formula (I) can additionally be used in anticorrosive formulations, in particular for the purpose of preventing corrosion at high temperatures.
[0163] Furthermore, the copolymer of formula (I) and the formulations comprising it can also be used to inhibit the corrosion of reinforcing steel in reinforced concrete. When both the copolymer of formula (I) and the formulations comprising it are introduced into the concrete mixture before it is cast and hardened, and when the copolymer of formula (I) and the formulations comprising it are applied to the concrete surface after the concrete has hardened, the corrosion inhibition effect in reinforced concrete is achieved.
[0164] Apart from the purpose of corrosion protection for metals, the copolymers of formula (I) can also serve to manipulate further properties of the solids or films obtained from the formulations containing the organopolysiloxanes of the invention or from the formulations containing the copolymers of formula (I), for example: -Control of electrical conductivity and electrical resistance -Control of compound leveling properties -Controlling the gloss of wet or cured films or objects -Improved weather resistance stability -Improved chemical resistance -Improved color stability - Reduced tendency to choke - increase or decrease of static and sliding friction on solids or thin films obtained from formulations comprising copolymers of formula (I) -Stabilization or destabilization of foam in formulations comprising the formulation - improved adhesion of formulations comprising copolymers of formula (I) to substrates -Controlling the wetting and dispersing properties of fillers and pigments - Controlling the rheological properties of formulations comprising the organopolysiloxanes of the present invention - mechanical properties, such as flexibility, scratch resistance, elasticity, extensibility, bending, friction properties, rebound properties, hardness, density, tear propagation resistance, compression set, behavior at different temperatures, expansion coefficient, abrasion resistance and thermal conductivity, flammability, gas permeability, resistance to water vapor, heat, chemicals, weather and radiation, control of the sterility of solids or thin films comprising the copolymers of formula (I) or formulations comprising them; Control of electrical properties, e.g., dielectric loss factor, breakdown resistance, dielectric constant, tracking current resistance, arc resistance, surface resistance, breakdown resistance - flexibility, scratch resistance, elasticity, extensibility, bending, fracture properties, rebound properties, hardness, density, tear propagation resistance, compression set, behavior at different temperatures of solids or thin films obtainable from formulations comprising copolymers of formula (I).
[0165] Examples of applications in which the copolymers of formula (I) can be used to manipulate the above-specified properties are the manufacture of coatings and impregnating agents, and the manufacture of coatings and coverings on substrates (metal, glass, wood, mineral substrates, synthetic and natural fibers, etc.) for textiles, carpets, rugs, or other articles that can be made from textiles, leather, plastics (films, etc.) and moldings that can be obtained from them. Considering the appropriate selection of the formulation components, the copolymers of formula (I) may be used in formulations as additives for the purposes of defoaming, leveling promotion, hydrophobization, hydrophilization, filler and pigment dispersion, filler and pigment wetting, substrate wetting, promoting surface smoothness, reducing static and sliding friction on the surface of the cured mass that can be obtained from the additive formulation. The copolymers of formula (I) may be incorporated into liquid or cured solid elastic masses. They may be used here for the purpose of reinforcing or improving other use properties, such as transparency, heat resistance, yellowing tendency, weather resistance control, etc.
[0166] All symbols above in the above formulae are each defined independently of each other: In all formulae, the silicon atom is tetravalent. EXAMPLES
[0167] The following examples serve to further clarify the invention, but should be considered as illustrative and not limiting.
[0168] All percentages are by weight. Unless otherwise specified, all operations are carried out at room temperature of 23° C. and standard pressure (1.013 bar).
[0169] Unless otherwise specified, all data describing the product properties are applicable at room temperature of 23° C. and standard pressure (1.013 bar).
[0170] The instruments are off-the-shelf laboratory equipment supplied commercially by several instrument manufacturers. Ph means the phenyl radical =C6H5-. Me means the methyl radical =CH3-. Me2 correspondingly means two methyl radicals. PPE means polyphenylene ether. HCl means hydrochloric acid.
[0171] In this document, materials are characterized by the reporting of data obtained by instrumental analysis. The underlying measurements are either performed by publicly available standards or confirmed by specifically developed methods. To ensure clarity of the teachings given, the methods used are specified hereafter.
[0172] In all examples, references to parts and percentages are by weight unless otherwise specified.
[0173] viscosity: Unless otherwise specified, the viscosity is determined by rotational viscometer measurements in accordance with DIN EN ISO 3219. Unless otherwise specified, all viscosity figures are applicable at 25° C. and standard pressure of 1013 mbar.
[0174] Refractive Index: The refractive index is determined in the visible wavelength range of 589 nm at 25° C. and a standard pressure of 1013 mbar according to DIN 51423 unless otherwise specified.
[0175] Transmittance: The transmittance is determined by a UV / visible spectrometer. An example of a suitable device is the Analytik Jena Specord 200.
[0176] The measurement parameters used were: range 190-1100 nm, step width: 0.2 nm, integration time: 0.04 s, measurement mode: step operation. First, a reference value (background) is measured. A quartz plate fixed in a sample holder (quartz plate dimensions: H×W approx. 6×7 cm, thickness approx. 2.3 mm) is placed in the sample beam path and measured against air.
[0177] The sample is then measured: a quartz plate with the coated sample fixed in a sample holder - the layer thickness of the coated sample is approximately 1 mm - is placed in the sample beam path and measured against air. The internal offset to the background spectrum gives the transmittance spectrum of the sample.
[0178] Molecular composition: The molecular composition is 1 H nuclei and 29 It is determined by a nuclear magnetic resonance spectrometer equipped with a measurement of Si nuclei (for terminology, see ASTM E 386: High Resolution Magnetic Resonance Spectroscopy (NMR): Terminology and Symbols).
[0179] 1 H NMR measurement explanation Solvent: CDCl3 99.8%d Sample concentration: approx. 50mg / 1ml CDCl3 in 5mm NMR tube Measurements without TMS added, reference spectrum of CHCl3 radical in CDCl3 at 7.24 ppm Spectrometer: Bruker Avance I 500 or Bruker Avance HD 500 Sample head: 5mm BBO sample head or SMART sample head (Bruker) Measurement parameters: Pulprog=zg30 TD=64k NS=64 or 128 (depending on the sensitivity of the sample head) SW=20.6ppm AQ=3.17 seconds D1=5 seconds SFO1=500.13MHz O1=6.175ppm Processing parameters: SI=32k WDW=EM LB=0.3Hz
[0180] Depending on the spectrometer type used, individual adjustments of the measurement parameters may be required.
[0181] 29 Explanation of Si NMR measurements Solvent: C6D6 99.8%d / CCl4 1:1 (vol / vol) containing 1 wt% Cr(acac)3 as relaxation agent Sample concentration: approx. 2g / 1.5ml solvent in 10mm NMR tube Spectrometer: Bruker Avance 300 Sample head: 10mm 1H / 13C / 15N / 29Si glass-free QNP sample head (Bruker) Measurement parameters: Pulprog=zgig60 TD=64k NS=1024 (depending on the sensitivity of the sample head) SW=200ppm AQ=2.75 seconds D1=4 seconds SFO1=300.13MHz O1=-50ppm Processing parameters: SI=64k WDW=EM LB=0.3Hz
[0182] Depending on the spectrometer type used, individual adjustments of the measurement parameters may be required.
[0183] Molecular weight distribution: The molecular weight distribution is determined as weight average Mw and number average Mn by using the method of gel permeation chromatography (GPC, or size exclusion chromatography (SEC)) with polyester standards and a refractive index detector (RI detector). Unless otherwise specified, THF is used as the eluent and DIN 55672-1 is applied. The polydispersity is the quotient Mw / Mn.
[0184] Glass Transition Temperature: The glass transition temperature is determined by dynamic differential calorimetry (differential scanning calorimetry, DSC) according to DIN 53765, perforated crucible, heating rate 10 K / min.
[0185] Granularity determination: The particle size was determined by the method of dynamic light scattering (DLS), including the determination of the zeta potential.
[0186] The following auxiliary agents and reagents were used for the determination: 10 x 10 x 45 mm polystyrene cuvettes, disposable Pasteur pipettes, ultrapure water.
[0187] The sample to be analyzed is homogenized and introduced bubble-free into the analysis cuvette.
[0188] Measurements are carried out at 25° C. after an equilibration time of 300 seconds using high resolution and automatic adjustment of the measurement time.
[0189] The reported values are always based on D(50), which should be taken as the volume mean particle size at which 50% of all particles analyzed have a volume mean diameter less than the stated D(50).
[0190] Determination of dielectric properties: Df, Dk The dielectric properties are determined at 10 GHz by the split cylinder resonance method using a Keysight / Agilent E8361A network analyzer according to IPC TM 650 2.5.5.13.
[0191] Microscopy Procedure: The micro / nanostructures were characterized by optical or transmission electron microscopy. Optical microscope: Sample preparation: 1 drop of sample (undiluted) on a microscope slide; cover with a coverslip Equipment: LEICA DMRXA2 equipped with a LEICA DFC420 CCD camera (2592 x 1944 pixels) Image: Transmitted light - interference contrast, various magnification levels Transmission electron microscope: Sample preparation: 1 drop of sample on coated TEM grid (dilution 1:20, adjust as needed); ignite contrast agent if necessary; dry at RT Equipment: ZEISS LIBRA 120 equipped with a Sharp Eye CCD camera (1024 x 1024 pixels) Images: Excitation voltage 120 kV; TEM bright field; various magnification steps
[0192] Peel Strength Test: The adhesion of metal layers laminated onto composite layers with or without reinforcement was determined according to method IPC-TM 650 2.4.8 “Peel Strength of Metallic Clad Laminates” “as received”, i.e. without thermal stress or exposure.
[0193] 35μm copper foil, mass 285±10g / m 2 , 10-point average roughness Rz≦8μm, arithmetic mean roughness Ra≦0.4μm were laminated on both sides of a 100μm thick composite layer, cured and laminated by application of 2.0MPa, 30mmHg column at 200℃ for 180min.
[0194] Example 1: Preparation of the copolymer of the present invention by oxidative coupling 1.1. Hydroxyaryl-functional three-dimensional crosslinked polyorganosiloxanes: Composition percentage (mol%) of polyorganosiloxane 700g [(C6H5)SiO 3 / 2 ] 55.8 [(C6H5)(OH)2SiO 1 / 2 ] 2.0 [(C6H5)(OH)SiO 2 / 2 ] 32.9 [(CH3)2(H)SiO 1 / 2 ] 9.3, Mw = 4391 g / mol, Mn = 2014 g / mol, dissolved in 500 g of toluene. 4-Allyl-2-methoxyphenol 90 g (= 0.55 mol) (eugenol, C 10 H 12 O2, 164.2 g / mol) is added to this solution at room temperature of 23 ° C and the mixture is homogenized by stirring with a laboratory paddle stirrer. The solution is heated to an internal temperature of 80 ° C and the heating power of the heating equipment is adjusted so that this temperature is constant. At this temperature, 0.6 g of a 4% platinum (IV)-containing solution of hexachloroplatinic (IV) acid in propanediol is added, which means that 30 ppm of platinum (IV) are available for catalysis for a total of 790 g of the mass of the coreactants. The solution is stirred for 2 hours without changing the heating power of the heating equipment. The reaction mixture is then cooled to room temperature of 23 ° C and filtered through a filter plate with a pore size of 1 μm. The solution is adjusted to a concentration of 50% toluene. A transparent yellowish solution is obtained. The eugenol-functional silicone resin present is 29 The composition percentage (mol%) [(C6H5)SiO 3 / 2 ] 67.7 [(C6H5)(OH)2SiO 1 / 2 ] 1.0 [(C6H5)(OH)SiO 2 / 2 ] 22.0 [(CH3)2(H)SiO 1 / 2 ] 4.0 [(CH3)2(C 10 H 13 O2)SiO 1 / 2 ] 5.3 By SEC, it has Mw=5596 g / mol and Mn=2281 g / mol. The number of hydroxyaryl functional radicals relative to the total Si-bonded radicals is 3.7 mol%.
[0195] 1.2. Oxidative coupling of phenols with polyorganosiloxanes from 1.1.: 0.5m of pure oxygen 3A constant flow of 100 ml / h is set up by an initial charge of 200 ml toluene, 0.82 g copper(II) bromide and 21.8 g di-n-butylamine. A mixture of 70 g polyorganosiloxane from 140 g (1.15 mol) 1.1 and 2,6-xylenol (122.2 g / mol) in 200 ml toluene is metered into this initial charge, without exceeding an internal temperature of 30° C. After the metered addition is over, the reaction mixture is stirred for a further 3 hours without further heating. The reaction is stopped by adding 60 ml acetic acid, and the water-soluble constituents are then removed by washing three times with 200 ml demineralized water each time. After filtration through a 1 μm filter plate, the volatile constituents are removed under reduced pressure at 120° C. As soon as a final vacuum of 10 mbar has been achieved, the mixture is heated for a further 2 hours in order to remove all constituents that are volatile under these conditions. 196 g of a brown, transparent product are obtained which is solid at room temperature and can be readily dissolved in both toluene and xylene at a concentration of 50% by weight to give a brown, transparent solution of low viscosity. 29 By Si NMR spectroscopy, the resulting copolymers were characterized by the following composition percentages (mol%): [(C6H5)SiO 3 / 2 ] 66.3 [(C6H5)(OH)2SiO 1 / 2 ] 1.5 [(C6H5)(OH)SiO 2 / 2 ] 23.0 [(CH3)2(H)SiO 1 / 2 ] 3.8 [(CH3)2(C 10 H 13 O2)SiO 1 / 2 ] 0.3 [(CH3)2(poly-2,6-dimethylphenol)SiO 1 / 2 ] 5.1 has.
[0196] The molecular weight is determined as Mw=17234 g / mol, Mn=6798 g / mol. The proportion of poly-2,6-dimethylphenol units in the polyorganosiloxane-polyphenylene ether copolymer is: 162% by weight according to H NMR. The proportion of OH groups in the copolymer (together with phenolic OH groups and silanol groups) is 0.9% by weight. Taking into account the molecular weight of OH of 17 g / mol, this means that 9 mol of OH are present in the molecule with Mw=17234 g / mol.
[0197] This copolymer, hereinafter referred to as 1.2.1., is not yet in accordance with the invention since it does not yet contain olefinically unsaturated groups, which are incorporated as described hereinafter.
[0198] A 50% by weight solution of copolymer 1.2.1. is prepared by dissolving 100 g (5.8 mmol) of this copolymer in 100 g of toluene. The residual water content of the solution is determined by Karl Fischer titration and is 364 ppm.
[0199] First 21.2 g (0.18 mol) of dimethylvinylchlorosilane are metered in, then 17.4 g (0.22 mol) of pyridine. The first metered addition takes place over 30 min, the second over 45 min. An exothermic temperature rise is observed. Here too the temperature is limited to 40° C. by adjusting the metered addition rate. When the metered addition is complete, the mixture is stirred for a further 60 min in order to complete the reaction.
[0200] After the reaction is complete, the mixture is washed three times with 200 ml of demineralized water each time, removing the aqueous layer each time.
[0201] In each case, the mixture is stirred for 30 minutes for phase separation, then the stirrer is turned off and the phases are allowed to separate. The aqueous phase is separated at the bottom and discarded. This operation is repeated until the residual HCl content in the organic phase, determined by acid-base titration according to the conventional technique, is <20 ppm.
[0202] If the aqueous phase settles to the top, a 10% sodium chloride containing aqueous solution is used for washing rather than demineralized water, otherwise the procedure is the same.
[0203] After the final phase separation, the residual HCl content in the organic phase is <20 ppm. As already described above, the solvent is removed by distillation at 120° C. and a reduced pressure of 10 mbar. Here too, the distillation is continued under these conditions for 2 hours in order to remove all volatile components.
[0204] A brown, transparent, solid reaction product is obtained having a molecular weight of Mw=18843 g / mol, Mn=6920 g / mol. 29 By Si NMR spectroscopy, the resulting copolymers were characterized by the following composition percentages (mol%):
[0205] [(C6H5)SiO 3 / 2 ] 84.6 [(C6H5)(OH)SiO 2 / 2 ] 3.1 [(CH3)2(H)SiO 1 / 2 ] 3.5 [(CH3)2(C 10 H 13 O 1.5 )SiO 1 / 2 ] 0.3 [(CH3)2(poly-2,6-dimethylphenol)SiO 1 / 2 ] 4.8 [(CH3)2(CH2=HC)SiO 1 / 2 ] 6.8 , 6.8 mol% [(CH3)2(CH2=HC)SiO 1 / 2 The ] unit must be bonded to the former OH group, since there is no alternative under the selected reaction conditions.
[0206] The residual OH content is 1 It is still 0.05% by weight as determined by 1 H NMR spectroscopy.
[0207] This copolymer is hereafter referred to as 1.2.2.
[0208] Copolymer 1.2.2. contains more than 30% by weight of polyarylene ether units, more than 0.5 mol% of olefinically unsaturated groups and the proportion of three-dimensionally crosslinked silicone units in the polyorganosiloxane backbone is more than 40 mol%, in particular more than 50 mol%, which means that all the criteria of inventiveness are met.
[0209] In addition, Si-H groups are present so that curing can occur either by hydrosilylation or by free radical means.
[0210] Example 2: Preparation of the copolymer of the present invention by oxidative coupling 2.1. Hydroxyaryl-functional three-dimensional crosslinked polyorganosiloxanes: Polyorganosiloxane composition percentage (mol%) of 700g [(C6H5)SiO 3 / 2 ] 43 [(C6H5)(OH)2SiO 1 / 2 ] 0.7 [(C6H5)(OH)SiO 2 / 2 ] 29.3 [(CH3)2(H)SiO 1 / 2 ] 27.0 , Mw = 3419 g / mol, Mn = 1741 g / mol, dissolved in 500 g of toluene. 120 g (= 0.73 mol) of 4-allyl-2-methoxyphenol (eugenol, C 10 H 12 O2, 164.2 g / mol) and 100 g (=0.82 mol) of allyl methacrylate (CH 10 O2 (126.16 g / mol) is added to this solution at room temperature of 23°C and the mixture is homogenized by stirring with a laboratory paddle stirrer. The solution is heated to an internal temperature of 80°C and the heating power of the heating device is adjusted so that this temperature is constant. At this temperature, 0.69 g of a 4% platinum(IV)-containing solution of hexachloroplatinic acid in propanediol is added, which means that 30 ppm of platinum(IV) is available for catalysis for an amount of 920 g of co-reactant. The further procedure is the same as in Example 1.1. and the results are as follows: 29 Si NMR composition percentage (mol%) [(C6H5)SiO 3 / 2 ] 44.9 [(C6H5)(OH)2SiO 1 / 2 ] 0.7 [(C6H5)(OH)SiO 2 / 2 ]27.4 [(CH3)2(H)SiO 1 / 2 ] 11.6 [(CH3)2SiO 2 / 2 ] 1.0 [(CH3)2(C 10 H 13 O2)SiO 1 / 2 ] 6.5 [(CH3)2(C7H 11 O2)SiO 1 / 2 ] 7.9 [(CH3)2SiO 2 / 2 The formation of the ] unit is most likely explained by the loss of hydrogen during the reaction and the formation of siloxane bonds.
[0211] The molecular weights are Mw=4369 g / mol and Mn=2018 g / mol by SEC. The number of hydroxyaryl functional radicals relative to the total Si-bonded radicals is 3.6 mol%. The number of olefinically unsaturated groups is 4.3 mol%.
[0212] 2.2. Oxidative coupling of phenols with polyorganosiloxanes from 2.1.: The procedure corresponds to that described in 1.2. 187 g of a brown transparent product is obtained, which is solid at room temperature and can be easily dissolved in both toluene and xylene at a concentration of 50% by weight, giving a brown transparent solution of low viscosity. 29 By Si NMR spectroscopy, the resulting copolymers were characterized by the following composition percentages (mol%): [(C6H5)SiO 3 / 2 ] 50.2 [(C6H5)(OH)2SiO 1 / 2 ] 0.5 [(C6H5)(OH)SiO 2 / 2 ] 22.4 [(CH3)2(H)SiO 1 / 2 ] 11.2 [(CH3)2SiO 2 / 2 ] 1.4 [(CH3)2(C 10 H 13 O2)SiO 1 / 2 ] 0.6 [(CH3)2(poly-2,6-dimethylphenol)SiO1 / 2 ] 5.9 [(CH3)2(C7H 11 O2)SiO 1 / 2 ] 7.8 has.
[0213] The molecular weight is determined as Mw=12334 g / mol, Mn=4987 g / mol. The proportion of poly-2,6-dimethylphenol units in the polyorganosiloxane-polyphenylene ether copolymer is: 1 63% by weight according to H NMR. The proportion of OH groups in the copolymer (together with phenolic OH groups and silanol groups) is 0.8% by weight.
[0214] This copolymer is hereafter referred to as 2.2.
[0215] It contains more than 30% by weight of polyarylene ether units, more than 0.5 mol% of olefinically unsaturated groups and the proportion of three-dimensionally crosslinked silicone units in the polyorganosiloxane backbone is more than 40 mol%, in particular more than 50 mol%, which means that all the criteria for inventiveness are met.
[0216] In addition, the presence of Si-H groups allows curing to be effected both by hydrosilylation or by free radical means.
[0217] Example 3: Preparation of the copolymer of the present invention by oxidative coupling (methyl resin without excess Si-H) 3.1. Hydroxyaryl-functional three-dimensional crosslinked polyorganosiloxanes: 700g of polyorganosiloxane with composition percentage (mol%) [(CH3)SiO 3 / 2 ] 56 [(CH3)(OH)2SiO 1 / 2 ] 1.7 [(CH3)(OH)SiO 2 / 2 ] 28.3 [(CH3)2(H)SiO 1 / 2 ] 14, Mw = 3965 g / mol, Mn = 1984 g / mol, dissolved in 500 g of toluene. 120 g (= 0.73 mol) of 4-allyl-2-methoxyphenol (eugenol, C 10 H 12 O2, 164.2 g / mol) and 100 g (=0.82 mol) of allyl methacrylate (CH 10 O2, 126.16 g / mol) is added to this solution at room temperature of 23° C. and the solution is homogenized by stirring using a laboratory paddle stirrer. Further procedures are as described in Example 2, giving the following results: 29 Composition percentage by Si NMR (mol%): [(CH3)SiO 3 / 2 ] 61.2 [(CH3)(OH)2SiO 1 / 2 ] 1.2 [(CH3)(OH)SiO 2 / 2 ] 23.6 [(CH3)2(C 10 H 13 O2)SiO 1 / 2 ] 6.3 [(CH3)2(C7H 11 O2)SiO 1 / 2 ] 7.7 , and molecular weight by SEC of Mw=4259 g / mol and Mn=2028 g / mol. The number of hydroxyaryl functional radicals relative to the total Si-bonded radicals is 4.1 mol %. The number of olefinically unsaturated groups is 5.0 mol %.
[0218] 3.2. Oxidative coupling of phenols with polyorganosiloxanes from 3.1.: The procedure corresponds to that described in 1.2. 178 g of a brown transparent product is obtained, which is solid at room temperature and can be easily dissolved in both toluene and xylene at a concentration of 50% by weight, giving a brown transparent solution of low viscosity. 29 By Si NMR spectroscopy, the resulting copolymers were characterized by the following composition percentages (mol%): [(CH3)SiO 3 / 2 ] 63.7 [(CH3)(OH)2SiO 1 / 2 ]0.7 [(CH3)(OH)SiO 2 / 2 ] 21.6 [(CH3)2(C 10 H 13 O2)SiO 1 / 2 ] 0.3 [(CH3)2(poly-2,6-dimethylphenol)SiO 1 / 2 ] 5.9 [(CH3)2(C7H 11 O2)SiO 1 / 2 ] 7.8 .
[0219] The molecular weight is determined as Mw=13394 g / mol, Mn=5094 g / mol. The proportion of poly-2,6-dimethylphenol units in the polyorganosiloxane-polyphenylene ether copolymer is: 1 60% by weight according to H NMR.
[0220] This copolymer is hereafter referred to as 3.2.
[0221] It contains more than 30% by weight of polyarylene ether units, more than 0.5 mol% of olefinically unsaturated groups and the proportion of three-dimensionally crosslinked silicone units in the polyorganosiloxane backbone is more than 40 mol%, in particular more than 50 mol%, which means that all the criteria for inventiveness are met.
[0222] In the absence of Si-H groups, curing can only proceed by means of free radicals.
[0223] Example 4: Copolymers of the invention functionalized with chloropropionyl chloride The copolymer 1.2.1. is further worked up as follows: A 50% by weight solution of copolymer 1.2.1. is prepared by dissolving 100 g (5.8 mmol) of this copolymer in 100 g of toluene.
[0224] 34.4 g (0.27 mol) of 3-chloropropionyl chloride (126.97 g / mol) are metered in and the mixture is stirred for 2 hours at 80° C. After this, it is cooled to 50° C. and 33.5 g (0.33 mol) of triethylamine (101.19 g / mol) are metered in. After the metered addition has ended, stirring is continued for 60 minutes at 50° C. in order to complete the reaction.
[0225] The aqueous work-up is carried out as in Example 1.
[0226] A brown, transparent, solid reaction product is obtained having a molecular weight of Mw=19438 g / mol, Mn=7020 g / mol. 29 By Si NMR spectroscopy, the resulting copolymers were characterized by the following composition percentages (mol%): [(C6H5)SiO 3 / 2 ] 90.8 [(CH3)2(H)SiO 1 / 2 ] 1.2 [(CH3)2SiO 2 / 2 ] 2.2 [(CH3)2(C 13 H 16 O4)SiO 1 / 2 ] 0.4 [(CH3)2(Poly-2,6-dimethylphenol-O(O=)C-CH=CH2)SiO 1 / 2 ] 5.4 .
[0227] The radical (poly-2,6-dimethylphenol-O(O=)C-CH=CH2) refers to a polyarylene ether radical linked to the polyorganosiloxane backbone by eugenol groups and acrylate-functionalized on the terminal phenolic OH groups by reaction with 3-chloropropionyl chloride.
[0228] Radical (C 13 H 16 O4) refers to an acrylate-functionalized eugenol radical.
[0229] The Si-acetyloxy bond is unstable under the post-hydrolysis treatment conditions and is broken, contributing to the polyorganosiloxane network [(C6H5)SiO3 / 2
[0046] - groups, so that under the selected conditions there are no acrylate radicals attached to the polyorganosiloxane backbone. The acrylic acid-amine adduct is removed by aqueous workup.
[0230] In post-treatment, some of the Si-H groups are lost by elimination of hydrogen hydride, which is [(CH3)2SiO 2 / 2 ]- group is generated.
[0231] This copolymer is hereafter referred to as 4.1.
[0232] Example 5: Copolymers of the invention made from bisphenol A and phenol The polyorganosiloxane according to example 2.1. is subjected to oxidative coupling as follows: The procedure corresponds to that described in Example 2.2., except that 122 g (1 mol) of 2,6-xylenol (122.2 g / mol) and 18 g (0.06 mol) of 2,2'-diallylbisphenol A (308.41 g / mol) were dissolved in 200 ml of toluene and metered in.
[0233] Obtain a copolymer with the following composition percentages ( 29 mol% by Si NMR: [(C6H5)SiO 3 / 2 ] 51.9 [(C6H5)(OH)SiO 2 / 2 ] 21.2 [(CH3)2(H)SiO 1 / 2 ] 10.9 [(CH3)2SiO 2 / 2 ] 1.7 [(CH3)2(C 10 H 13 O2)SiO 1 / 2 ] 0.3 [(CH3)2(Poly-2,6-dimethylphenol-diallyl bisphenol A copolymer)SiO 1 / 2 ] 6.2 [(CH3)2(C7H 11 O2)SiO 1 / 2 ] 7.8 .
[0234] The molecular weight is determined as Mw=18443 g / mol, Mn=6198 g / mol.
[0235] This copolymer is hereafter referred to as 5.1.
[0236] Example 6: Use of crosslinked siloxane units 6.1. Preparation of Hydroxyaryl-Functional Crosslinked Polyorganosiloxanes In contrast to Example 2.1, 2,6-dimethyl-4-allylphenol (=4-allyl-2,6-xylenol, C ) was used rather than eugenol. 11 H 14 The procedure of Example 2.1 was repeated, except that 178 g (=1.1 mol) of polyorganosiloxane [(CH)SiO2, Mw=162.2 g / mol] was used. 3 / 2 ] 13.1 [(CH3)(OH)SiO 2 / 2 ] 0.9 [(CH3)O 2 / 2 Si-CH2-CH2-Si(CH3)O 2 / 2 ] 61.7 [(CH3)2(H)SiO 1 / 2 ] 24.3 A methacrylate- and hydroxyaryl-functional polyorganosiloxane is prepared using 1,2-dimethylphenylsiloxane, Mw=1569 g / mol, Mn=948 g / mol, with the following results: 29 By Si NMR, a hydroxyaryl-functional polyorganosiloxane was obtained with the following composition percentages (mol %): [(CH3)SiO 3 / 2 ] 13 [(CH3)(OH)SiO 2 / 2 ] 11 [(CH3)O 2 / 2 Si-CH2-CH2-Si(CH3)O 2 / 2 ] 61.6 [(CH3)2(H)SiO 1 / 2 ] 0,1 [(CH3)2(C 11 H 15 O2)SiO 1 / 2 ]13.1 [(CH3)2(C7H 11 O2)SiO 1 / 2 ] 11.2 , Mw = 2304 g / mol, Mn = 1399 g / mol. This polyorganosiloxane will hereafter be referred to as 6.1.
[0237] 6.2. Preparation of the copolymers of the invention of formula (I) by oxidative coupling Similar to the procedure described in Example 2.2, 6.1. was used to prepare the polyarylene ether-polysiloxane copolymer of the present invention by oxidative coupling. The final product, hereafter referred to as 6.2., had the following composition percentages: 29 % by Si NMR: [(CH3)SiO 3 / 2 ] 13.3 [(CH3)(OH)SiO 2 / 2 ] 10.7 [(CH3)O 2 / 2 Si-CH2-CH2-Si(CH3)O 2 / 2 ] 61.6 [(CH3)2(H)SiO 1 / 2 ] 0.1 [(CH3)2(C 11 H 15 O2)SiO 1 / 2 ] 0.7 [(CH3)2(poly-2,6-dimethylphenol)SiO 1 / 2 ] 12.5 [(CH3)2(C7H 11 O2)SiO 1 / 2 ] 11.1 , Mw = 24678 g / mol, Mn = 8893 g / mol. This polyorganosiloxane will hereafter be referred to as 6.2.
[0238] Example 7: Leather Example: Oil-based copolymer from prior art U.S. Pat. No. 8,017,697 Example 1 of U.S. Patent No. 8,017,697 was reworked as described therein. In contrast to U.S. Patent No. 8,017,697, the requisite eugenol terminated polydimethylsiloxane having a chain length of 45 was not supplied by Momentive Performance Materials, but was prepared by the hydrosilylation method for eugenol in Example 1 of U.S. Patent No. 5,357,022. Product identity, particularly the correctness of the polydimethylsiloxane chain length and the success of the hydrosilylation reaction, are discussed below. 29 Confirmed by Si NMR spectroscopy.
[0239] The reaction conditions and the relative amounts of raw materials used were adjusted according to Table 2 of US Pat. No. 8,017,697. The following properties were determined for the resulting copolymer: Mw=49900g / mol, Mn=18500g / mol, Mw / Mn=2.7 Weight ratio of dimethylsiloxane in copolymer: 5.0%
[0240] No hint of unincorporated siloxanes in the copolymer was found, so a siloxane incorporation capacity close to 100% can be estimated. From this result, the rework of Example 1 according to U.S. Pat. No. 8,017,697 can be considered successful, and the product obtained is in accordance with the invention according to U.S. Pat. No. 8,017,697. It contains neither olefinically unsaturated groups nor network-forming siloxane moieties, as according to the prior art. This copolymer is hereafter referred to as 7.1.
[0241] Example 8: Use of the inventive and non-inventive organopolysiloxanes according to Examples 1 to 7 for the manufacture of metal clad laminates The inventive and non-inventive polyorganosiloxanes obtained according to synthesis examples 1 to 7 were used as binders to produce copper clad laminates containing glass fiber reinforced composite layers. The following raw materials were used:
[0242] Copper foil: 35μm thick copper foil (285±10g / m2 ), 10-point average roughness Rz≦8μm and arithmetic mean roughness Ra≦0.4μm, purity ≧99.8%.
[0243] Glass fiber: E-glass fiber from Changzhou Xingao Insulation Materials Co. Ltd., type 1080E, thickness 0.055±0.012mm, 47.5±2.5g / m 2 .
[0244] All organopolysiloxane-polyarylene ether copolymers were used as xylene solutions, which contained 35% by weight each of copolymer and initiator, and 65% by weight xylene.
[0245] To initiate the curing of the olefinically unsaturated copolymers 1.2.2., 2.2., 3.2., 4.1., 5.1. and 6.2., the organopolysiloxanes were mixed with 1% by weight of dicumyl peroxide, in each case relative to the amount of polyorganosiloxane used, which was homogeneously distributed in the resin matrix by stirring. The non-inventive copolymer 7.1. was treated once in the same way for comparison purposes, although it is not chemically possible in this way to achieve curing and its crosslinking. In addition, 7.1. was used to prepare a chemically curable binder formulation by preparing a chemically curable mixture according to the description of Example 1 of EP 0 592 145. The weight percentages which follow in the present invention are relative to 100% of the final formulation.
[0246] According to Example 1 of EP 0 592 145, 21.7 wt% of 7.1. was dissolved in 65.1 wt% toluene and mixed with 8.9 wt% EPON 828 (Hexion Inc.), 3.3 wt% N,N'-1,3-phenylene bismaleimide and 1.1 wt% aluminum triacetylacetonate (=Al(acac)3), and the temperature and sequence were observed as specified in Example 1 of EP 0 592 145.
[0247] Test laminates were prepared from the resulting mixtures as further specified hereinafter.
[0248] Laminates of 1.2.2., 2.2., 3.2., 4.1., 5.1. and 6.2. were produced by impregnating, layer by layer, 30x30 cm glass fibre layers with the respective copolymers in the form of a xylene solution using an air-bleeding roller, without any air bubbles. The procedure with 7.1. was carried out in the same way, except that in this example a solution prepared specifically for the purpose according to the prior art as described above was used. To ensure comparability, copolymers 1.2.2., 2.2., 3.2., 4.1., 5.1. and 6.2. as xylene solutions as specified above were similarly adjusted to a solids content of about 35% by weight, including initiator.
[0249] Here, a glass fiber layer was placed on a dimensionally stable, flat stainless steel base, to which a layer of copper foil was applied, followed by a first layer of glass fiber on top. All three layers of glass fiber fabric were successfully impregnated. The impregnated fabric was dried to constant weight at 60° C. in a vacuum drying cabinet at 10 mbar, to remove the solvent if necessary. A second layer of copper foil was then applied on top of the impregnated glass fiber layer, and a further dimensionally stable stainless steel plate was placed on top. The laminate was baked in a heated press at 200° C. for 120 minutes, at a pressure of 2 MPa and a reduced pressure of 30 mbar. This results in a copper clad laminate with a total thickness of 260±20 μm.
[0250] The dielectric properties were determined according to IPC TM 650 2.5.5.13 using a Keysight / Agilent E8361A network analyzer by the split cylinder resonance method at 10 GHz. The following values were obtained:
[0251] [Table 1]
[0252] D of copper clad laminates made from the copolymers of the present inventionf Value and D k The values are the D values obtained for copolymers from the procedure according to the prior art. f Value and D k Since the minimum dielectric loss factor and dielectric constant are oriented toward high frequency applications, the advantages of the present invention are clearly evident.
Claims
1. Formula (I): [O 3-a/2 R a Si-Y 1 (SiR a O 3-a/2 ) b ] c (R 1 SiO 3/2 ) d (R 2 2 SiO 2/2 ) e (R 3 3 SiO 1/2 ) f (SiO 4/2 ) g (I) The polyarylene ether-polysiloxane copolymer contains an olefinically unsaturated group, wherein in formula (I): Y 1 is a divalent to dodecavalent organic unsubstituted or heteroatom-substituted aliphatic, alicyclic or aromatic organic radical having 1 to 24 carbon atoms bonded to a silicon atom by a chemical bond or a Si bond; R, R 1 , R 2 and R 3 are independently the same or different and are a hydrogen radical, a hydroxyl radical, or a monovalent unsubstituted or heteroatom substituted Si—C or Si—O bond, an organic hydrocarbyl radical having 1 to 18 carbon atoms, which may be organofunctional, or a Si—C bonded polyarylene ether radical; Total R, R as 100% by weight 1 , R 2 and R 3 the ratio of the hydroxyl radicals and the Si—O bond radicals to the total amount of radicals is 5% by weight or less; Total R, R as 100% by weight 1 , R 2 and R 3 the proportion of said Si—C bonded polyarylene ether radicals relative to the total number of radicals is at least 10 wt. %; Total R, R as 100 mol% 1 , R 2 and R 3 the proportion of said olefinically or acetylenically unsaturated radicals relative to the total number of radicals is at least 0.5 mol %; The polyarylene ether radical has formula (II) or (III): 【Chemistry 1】 and in the formulae (II) and (III), R 4 , R 5 , R 6 , R 7 , R 8 , R 9 , R 10 , R 11 , R 12 and R 13 are independently a hydrogen radical, a monovalent hydrocarbyl group, a heteroatom-substituted hydrocarbyl group, an organofunctional radical, or (R 40 3 Si-) type silyl group, R 40 is R 3 has the definition of 4 ~R 12 The radical may be attached to the aromatic ring by a heteroatom; R 4 , R 5 and R 6 The radical may be a chemical bond or a divalent aliphatic, cycloaliphatic or aromatic hydrocarbyl radical having 1 to 12 carbon atoms, whereby the bond of the radical of formula (II) with the polyorganosiloxane backbone is established and at least one R 4 , R 5 Or R 6 The radical is a radical that establishes a bond with the polyorganosiloxane backbone, As far as chemically possible, R 4 ~R 12 Adjacent radicals from the radical group may be linked together to form the same cyclic saturated or unsaturated radical to form fused polycyclic structures, including both alicyclic and cyclic aromatic structures or mixed forms thereof; R 14 is a chemical bond or (-C 6 R 15 4 -) divalent optionally substituted arylene radicals of the form 15 Independently of these, R 9 , R 10 , R 11 Or R 12 has the same meaning as the radical -CR 16 2 is an alkylene radical of the form -, R 16 is R 15 Independently of R 15 may have the same meaning as 2 ) 2 O] l - or - [(OCH 2 CH (CH 3 ) 2 ) O] m a divalent glycol radical of the form -, where l and m are each independently an integer each having a value from 1 to 50, inclusive; 17 ) 2 O 2/2 -divalent silyloxy radicals of the form -[(CH 2 ) 3 Si-[O-Si(R 18 ) 2 ] n O-Si(CH 2 ) 3 -divalent siloxane radicals of the form -Si(R 19 ) 2 -type divalent silyl radicals, where R 17 , R 18 and R 19 are mutually independent, R 15 Independently of R 15 and n, in each occurrence, is an integer having a value in each occurrence from 0 to 500 (inclusive); a is an integer having a value of 0, 1 or 2, the indices a on either side of the Y group may assume these meanings independently of one another, such that different a's may independently have different values within the range of values specified, h has a value from 0 to 1000; b is an integer having a value from 1 to 11; c has a value between 0 and 0.9; d has a value between 0 and 1; e has a value between 0 and 0.5; f has a value between 0 and 0.6; g has a value between 0 and 0.2; c+d+e+f+g=1, at least c or d has a value other than 0, and the sum of c+d is at least 40% of the sum of c+d+e+f+g; i, in each occurrence, is an integer having a value from 0 to 50 (inclusive); j, in each occurrence, is an integer having a value from 0 to 10 (inclusive); k, in each case, is an integer having a value from 0 to 50, inclusive; provided that at least one polyarylene ether radical of formula (II) or (III) is present in each polyarylene ether-polysiloxane copolymer of formula (I); Copolymer.
2. The unsubstituted R, R 1 , R 2 , R 3 2. The copolymer of claim 1, wherein the radicals are selected from methyl, ethyl and n-propyl radicals and phenyl radicals.
3. The olefinically or acetylenically unsaturated R, R 1 , R 2 and R 3 3. Copolymers according to claim 1 or 2, wherein the radicals are selected from acrylate, methyl acrylate, methyl methacrylate, n-butyl acrylate, iso-butyl acrylate, t-butyl acrylate, 2-ethylhexyl acrylate, and norbornyl acrylate, vinyl, allyl, propenyl, butenyl, 1,3-butadienyl and isoprenyl radicals.
4. Total R, R as 100% by weight 1 , R 2 and R 3 The copolymer according to any one of claims 1 to 3, wherein the proportion of said Si-C bonded polyarylene ether radicals relative to the total of radicals is at least 30% by weight.
5. The copolymer according to any one of claims 1 to 4, which is a solid at 25°C and has a glass transition temperature of 25°C to 350°C.
6. The copolymer has the formula (R 2 2 SiO 2/2 ) e The copolymer according to any one of claims 1 to 5, which does not contain a unit of
7. A method for preparing a polyorganosiloxane-polyarylene ether copolymer of formula (I) according to any one of claims 1 to 6, comprising reacting an aryl hydroxyl radical of a polyorganosiloxane compound of formula (VII): [. 3-a/2 ( 31 a 3) 2 ()) 31 a . 3-a/2 ) b ] c () 32 three) 3/2 ) d () 33 2 three) 2/2 ) e () 34 3 three) 1/2 ) f ( ) - 4/2 ) g (().) In the formula (VII), R 31 is an R radical, R 32 is R 1 Radical, R 33 is R 2 Radical, R 34 is R 3 Radical, Y 2 Is Y 1 The radical is R 31 , R 32 , R 33 Or R 34 is a radical of formula (II) or Y 2 comprises such a radical of formula (II), then in this radical of formula (II) the index h is always 0 and R 13 The radical is always a hydrogen radical, and R 31 , R 32 , R 33 and R 34 cannot be a polyarylene ether radical of formula (III), and Y 2 may not contain a radical of formula (III), However, at least 1 mol% of all Si-bonded radicals are such that h=0 and R 13 = hydrogen, with a phenol of formula (VIIIa) or (VIIIb): 【Chemistry 2】 In the formulas (VIIIa) and (VIIIb), R 9 , R 10 , R 11 , R 12 and R 14 The radicals and j have the definitions given in claims 1 to 6. or by oxidative coupling of a mixture of (VIIIa) and (VIIIb).
8. Use of the copolymers according to any one of claims 1 to 6 as binders or additives in formulations, coating materials and impregnating agents and in the production of coatings and coverings produced therefrom on substrates.
9. Use of the copolymer according to any one of claims 1 to 6 for the production of metal foil clad laminates.
10. 10. The use according to claim 9, wherein the metal is selected from copper, stainless steel, gold, aluminium, silver, zinc, tin, lead and transition metals.